Materials comprising gem-metal atom pairs supported on support and methods related thereto
By loading multiple pairs of ligand metal atoms on the polymer support, a heterogeneous catalyst for catalytic coupling reaction was prepared, which solved the problem of weak active site control and support interactions in complex molecular transformation of existing catalysts, and achieved efficient, good selective catalytic effect and good recovery.
Patent Information
- Application Number
- CN202380062497.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-11
AI Technical Summary
Existing catalysts have problems with poor control of active site structure and weak interaction with support materials in catalyzing complex molecular transformation, resulting in limited applicability in cross-coupling reactions.
A material containing multiple pairs of geological metal atoms supported on a polymer support is developed through which heterogeneous catalysts are prepared, using the regular structure of the support to ensure the stability of the metal center and allow structural flexibility.
It is achieved to improve catalytic activity and selectivity in the catalytic coupling reaction, reduce metal leaching, and the catalyst has good recovery and stability.
Smart Images

Figure CN119816367A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure broadly relates to materials comprising geminal metal atoms supported on a support and methods of preparing the materials. The present disclosure also relates to catalysts comprising the materials and methods of catalyzing coupling reactions. Background Art
[0002] Homogeneous organometallic complexes are commonly used in transition metal-catalyzed reactions (e.g., cross-coupling reactions) that are essential for building molecular complexity in organic synthesis. Despite their unparalleled synthetic capabilities, there are many concerns about the use of homogeneous catalysts, including their potentially high production costs, environmental impacts associated with challenges in product separation and purification, catalyst recycling, and operation under harsh reaction conditions.
[0003] Turning to heterogeneous catalytic systems, the development of heterogeneous catalytic processes is very attractive for large-scale production to facilitate the separation, recovery and reuse of catalysts, and improves the adaptability to continuous flow synthesis. These potential advantages have triggered extensive research on immobilized organometallic complexes and nanostructured metal catalysts. However, although some have been successfully implemented in industry, their applicability in reactions (e.g., cross-coupling reactions) is still limited, mainly due to poor control of the active site structure or weak interactions with supports.
[0004] Heterogeneous single-atom catalysts (SACs) incorporating well-defined mononuclear metal sites have attracted interest due to their potential to overcome the shortcomings of previously developed catalytic solids. In particular, the presence of well-defined active sites in single-atom catalysts (SACs) has sparked interest in their potential for heterogeneous catalysis of organic synthesis. However, due to the restricted spatial environment and electronic quantum states, the architecture of mononuclear metal species stabilized on solid supports may not be optimal in catalyzing complex molecular transformations. It is believed that the support design must ensure the stability of the metal center while allowing structural flexibility to satisfy the catalytic cycle and achieve enzyme-like specific activities. Nevertheless, the chemical bonding between the metal center and the support required to prevent metal separation or agglomeration usually leads to a restricted spatial environment (e.g., high coordination number), limiting its ability to activate complex or multiple substrates simultaneously. These seemingly conflicting requirements have sparked a debate on whether mononuclear metal sites provide the best architecture for complex molecular transformations. Some researchers have hypothesized that customized multinuclear sites may be more effective, but controlled synthetic routes to other low-nuclearity catalysts remain limited.
[0005] Alternative approaches to exploit the synergistic effects between metal centers in SACs by controlling their spatial proximity have been investigated ( Fig.14). For example, many researchers have studied the performance of nanostructured metal catalysts (e.g., supported metal or metal oxide clusters or nanoparticles, fixed metal complexes and metal organic frameworks (MOFs) or zeolites) in cross-coupling applications. However, despite the fact that some materials have been commercialized, all of these categories of catalysts have inherent limitations that hinder their widespread industrial application. Specifically, supported metal-based clusters or nanoparticles may contain inaccessible metal atoms in the body of the structure, resulting in poor metal utilization, and in addition, the lack of atomic control and the resulting diversity of active sites in their structure limit their selectivity and also make it very challenging to understand the reaction mechanism. Since metal atoms in extended metal surfaces may strongly interact with reaction intermediates and ligands in coupling applications, high levels of metal leaching are common, which has triggered widespread debate about whether the observed performance is heterogeneous catalysis or homogeneous catalysis. MOFs and zeolites have inherent problems associated with poor accessibility to active sites in microporous channels, high cost of support materials, strong adsorption of organic components in the case of zeolites, and poor structural stability in the case of MOFs. Immobilized metal complexes operate under similar principles as organometallic complexes, meaning that ligands in the structure are removed and replaced during the catalytic cycle. This means that the coordination number of the metal center to the solid support will be very low and therefore the tendency to leach into the reaction mixture is high. Heterogeneous single-atom catalysts (SACs) with well-defined metal sites have attracted increasing attention due to their potential to bridge homogeneous and heterogeneous catalysis in the production of fine chemicals. However, the strong interactions between the single metal center and the support necessary to prevent metal separation or agglomeration generally require high coordination numbers, which makes them inactive due to their limited ability to activate multiple substrates simultaneously. These limitations require technological innovations in the design and synthesis of new efficient heterogeneous catalysts that are sufficiently active but also stable to leaching into organic coupling reactions.
[0006] In view of the above, it is necessary to solve or at least improve the above problems. In particular, it is necessary to provide a material comprising a geminal metal atom pair supported on a carrier, a catalyst comprising the material, and a related method thereof for solving or at least improving the above problems. Summary of the invention
[0007] In one aspect, a material is provided that includes a plurality of geminal metal atom pairs supported on a polymer support.
[0008] In one embodiment, each geminal metal atom pair comprises two single metal atoms that are not bonded to each other.
[0009] In one embodiment, the two single metal atoms are each bound to a different metal coordination site of the polymer support.
[0010] In one embodiment, the average distance between two single metal atoms is to
[0011] In one embodiment, each single metal atom is diagonally bonded to two different metal coordination sites of the polymer support.
[0012] In one embodiment, the material comprises a structure represented by the general formula (1); and a structure represented by the general formula (2):
[0013] –A 1 -M 1 -A 2 -(1)
[0014] –A 3 -M 2 -A 4 -(2)
[0015] in
[0016] M 1 and M 2 Each is independently a single metal atom;
[0017] M 1 and M 2 The two form a pair of geminal metal atoms; and
[0018] A 1 , A 2 , A 3 and A 4 Each is independently a metal coordination site of the polymer support.
[0019] In one embodiment, the material comprises 0.1 wt% to 50.0 wt% metal.
[0020] In one embodiment, the metal comprises a transition metal selected from the group consisting of copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), iron (Fe), manganese (Mn), chromium (Cr), vanadium (V), titanium (Ti), scandium (Sc), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), lanthanum (La), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), gold (Au), mercury (Hg), actinium (Ac), and combinations thereof.
[0021] In one embodiment, the metal is monovalent.
[0022] In one embodiment, the polymer support comprises an organic polymer comprising one or more atoms selected from the group consisting of carbon, nitrogen, phosphorus, sulfur, and combinations thereof.
[0023] In one embodiment, the polymer carrier comprises a polymer chain having two or more fused triazine rings.
[0024] In one embodiment, the material comprises a first shell comprising metal atoms and first atoms of a polymer support.
[0025] In one embodiment, the interatomic distance between the metal atom in the first shell and the first atom of the polymer support is to
[0026] In one embodiment, the material comprises a second shell comprising metal atoms and second atoms of the polymer support.
[0027] In one embodiment, the interatomic distance between the metal atom in the second shell and the second atom of the polymer support is to
[0028] In one aspect, a catalyst is provided, comprising a material disclosed herein.
[0029] In one aspect, a method for catalyzing a coupling reaction is provided, the method comprising:
[0030] (ai) providing the materials disclosed herein; and
[0031] (a-ii) mixing the material with two or more reactants to be coupled to obtain a coupling product.
[0032] In one embodiment, the coupling reaction comprises a cross-coupling reaction, a cross-coupling bond formation, a cycloaddition, a carbon-carbon bond formation, a carbon-heteroatom bond formation, an N-arylation, or a combination thereof.
[0033] In one embodiment, the reactant is selected from the group consisting of heteroaryl halides, aryl halides, substrates containing one or more hydroxyl groups, substrates containing one or more amino groups, substrates containing one or more amide groups, substrates containing one or more sulfonamide groups, substrates containing one or more alkynyl groups, substrates containing one or more thiol groups, substrates containing one or more electron-rich aromatic groups, substrates containing one or more electron-poor aromatic groups, alcohols, halogenated alcohols, deuterated alcohols, heterocyclic compounds, alkynes, thiols, azides, acetylenes, L-menthol, DL-menthol, stigmasterol, DL-isoborneol, galactose, 1,2,3,4-diacetonegalactose, testosterone, prednisolone, derivatives thereof, and combinations thereof.
[0034] In one aspect, a method of preparing a material disclosed herein is provided, the method comprising:
[0035] (i) reacting a metal source with a polymer support to obtain said material; and
[0036] (ii) Separating the materials.
[0037] In one embodiment, the method further comprises the step of exfoliating the material into nanostructures.
[0038] In one embodiment, the metal source comprises a metal salt selected from the group consisting of metal chlorides, metal fluorides, metal bromides, metal iodides, metal oxides, metal sulfates, metal sulfides, metal cyanides, metal thiocyanates, metal acetylides, metal acetates, metal hydroxides, metal hydrides, metal nitrates, metal phosphides, metal phosphates, metal carbonates, metal carbonate hydroxides, metal chlorates, metal arsenates, metal azides, metal acetylacetonates, metal perchlorates, metal triflates, metal tetrafluoroborates, metal benzoates, metal chromites, metal peroxides, and combinations thereof.
[0039] In one embodiment, the metal source comprises a divalent metal cation.
[0040] In one embodiment, the reacting step comprises adding 0.1 wt% to 50.0 wt% of the metal source.
[0041] In one embodiment, the reacting step includes adding 50.0 wt% to 99.9 wt% of the polymer carrier.
[0042] definition
[0043] The term "support" as used herein should be broadly interpreted as any substance that provides one or more sites for supporting / anchoring species, atoms, molecules, ions or particles. The sites can be active sites for supporting / anchoring metal species, atoms, molecules, ions or particles. The support can be a non-metallic support. Examples of supports include polymers, copolymers, block polymers, microparticles, nanoparticles and solid surfaces.
[0044] The term "alkyl" as a group or part of a group refers to a straight or branched aliphatic hydrocarbon group having 1 to 20 carbon atoms, 1 to 10 carbon atoms, 1 to 6 carbon atoms, or 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 carbon atoms. Examples of suitable straight and branched alkyl substituents include methyl, ethyl, n-propyl, 2-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, hexyl, amyl, 1,2-dimethylpropyl, 1,1-dimethylpropyl, pentyl, isopentyl, hexyl, 4-methylpentyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 2,2-dimethylbutyl, 3,3-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl The groups include 1,2,2-trimethylpropyl, 1,1,2-trimethylpropyl, 2-ethylpentyl, 3-ethylpentyl, heptyl, 1-methylhexyl, 2,2-dimethylpentyl, 3,3-dimethylpentyl, 4,4-dimethylpentyl, 1,2-dimethylpentyl, 1,3-dimethylpentyl, 1,4-dimethylpentyl, 1,2,3-trimethylbutyl, 1,1,2-trimethylbutyl, 1,1,3-trimethylbutyl, 5-methylheptyl, 1-methylheptyl, octyl, nonyl and decyl, etc. The groups may be terminal groups or bridging groups.
[0045] The term "alkenyl" as a group or part of a group means an aliphatic hydrocarbon group containing at least one carbon-carbon double bond and can be straight or branched, having 2 to 20 carbon atoms, 2 to 10 carbon atoms, 2 to 6 carbon atoms, or 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 carbon atoms in the chain. The group can contain multiple double bonds, and the orientation about each double bond is independently E or Z. Exemplary alkenyl groups include, but are not limited to, ethenyl, vinyl, allyl, 1-methylethenyl, 1-propenyl, 2-propenyl, 2-methyl-1-propenyl, 2-methyl-1-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1,3-butadienyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1,3-pentadienyl, 2, 4-pentadienyl, 1,4-pentadienyl, 3-methyl-2-butenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 1,3-hexadienyl, 1,4-hexadienyl, 2-methylpentenyl, 1-heptenyl, 2-heptenyl, 3-heptenyl, 1-octenyl, 2-octenyl, 3-octenyl, 1-nonenyl, 2-nonenyl, 3-nonenyl, 1-decenyl, 2-decenyl and 3-decenyl, etc. The group may be a terminal group or a bridging group.
[0046] The term "alkynyl" as a group or part of a group means an aliphatic hydrocarbon group containing at least one carbon-carbon triple bond and which may be straight or branched having 2 to 20 carbon atoms, 2 to 10 carbon atoms, 2 to 6 carbon atoms, or 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 carbon atoms in the chain. The group may contain multiple triple bonds. Exemplary alkynyl groups include, but are not limited to, ethynyl, propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-pentynyl, 2-pentynyl, 3-methyl-1-butynyl, 4-pentynyl, 1-hexynyl, 2-hexynyl, 5-hexynyl, 1-heptynyl, 2-heptynyl, 6-heptynyl, 1-octynyl, 2-octynyl, 7-octynyl, 1-nonynyl, 2-nonynyl, 8-nonynyl, 1-decynyl, 2-decynyl, and 9-decynyl, etc. The group may be a terminal group or a bridging group.
[0047] The term "aryl" as a group or part of a group means (i) an optionally substituted monocyclic or fused polycyclic aromatic carbocyclic ring (ring structure having all carbon ring atoms) preferably having 5 to 20 or 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 carbon atoms per ring. Examples of aryl include, but are not limited to, phenyl, tolyl, xylyl, naphthyl, anthracenyl, phenanthrenyl, fluorenyl, indenyl or indanyl, etc.
[0048] The term "heteroaryl" as a group or part of a group refers to a group containing an aromatic ring (preferably a 5- or 6-membered aromatic ring) having one or more carbon atoms (e.g., 1 to 6 carbon atoms) substituted by heteroatoms in the ring. Suitable heteroatoms may include nitrogen (N) or (NH), oxygen (O) and sulfur (S). Examples of heteroaryl include, but are not limited to, thiophene, benzothiophene, benzofuran, benzimidazole, benzoxazole, benzothiazole, benzisothiazole, naphtho[2,3-b]thiophene, furan, isoindolizine, xantholene, phenoxatine, pyrrole, imidazole, pyrazole, pyridine, pyrazine, pyrimidine, pyridazine, tetrazole, indole, isoindole, 1H-indazole, purine, quinone, In some embodiments, the present invention relates to quinoline, isoquinoline, phthalazine, naphthyridine, quinoxaline, cinnoline, carbazole, phenantridine, acridine, phenazine, thiazole, isothiazole, phenothiazine, oxazole, isoxazole, furazan, phenoxazine, 2-, 3- or 4-pyridyl, 2-, 3-, 4-, 5- or 8-quinolyl, 1-, 3-, 4- or 5-isoquinolyl, 1-, 2- or 3-indolyl, and 2- or 3-thienyl, etc. The group may be a terminal group or a bridging group.
[0049] The term "halogen" means chlorine, fluorine, bromine or iodine. The term "halide" means chloride, fluoride, bromide or iodide.
[0050] The term "optionally substituted" when used to describe a chemical structure or moiety refers to a chemical structure or moiety in which one or more of its hydrogen atoms are optionally replaced with a chemical moiety or functional group, such as an alcohol, alkoxy, alkanoyloxy, alkoxycarbonyl, alkenyl, alkyl (e.g., methyl, ethyl, propyl, tert-butyl), alkynyl, alkylcarbonyloxy (-OC(O)alkyl), amide (-C(O)NH-alkyl- or -alkylNHC(O)alkyl), amine (e.g., alkylamino, arylamino, arylalkylamino), aryl, aryloxy, azo, carbamoyl (-NHC(O)O-alkyl- or -OC(O)NH-alkyl), carbamyl (e.g., CONH 2 , and CONH-alkyl, CONH-aryl and CONH-arylalkyl), carboxyl, carboxylic acid, cyano, ester, ether (e.g., methoxy, ethoxy), halogen, haloalkyl (e.g., -CCl 3 , -CF 3 ,-C(CF 3 ) 3 ), heteroalkyl, isocyanate, isothiocyanate, nitrile, nitro, phosphodiester, sulfide, sulfonylamino (e.g., SO 2 NH 2 ), sulfone, sulfonyl (including alkylsulfonyl, arylsulfonyl and arylalkylsulfonyl), sulfoxide, thiol (e.g., mercapto, thioether) or urea (-NHCONH-alkyl-).
[0051] As used herein, the term "micro" should be broadly interpreted to include sizes from about 1 micron to about 1000 microns, from about 1 micron to less than about 1000 microns, from about 1 micron to about 900 microns, from about 1 micron to about 800 microns, from about 1 micron to about 700 microns, from about 1 micron to about 600 microns, from about 1 micron to about 500 microns, from about 1 micron to about 400 microns, from about 1 micron to about 300 microns, from about 1 micron to about 200 microns, or from about 1 micron to about 100 microns.
[0052] The term "nano" as used herein should be broadly interpreted as including the size in nanometer scale, i.e. less than about 1000nm, about 1nm to less than about 1000nm, about 1nm to about 900nm, about 1nm to about 800nm, about 1nm to about 700nm, about 1nm to about 600nm, about 1nm to about 500nm, about 1nm to about 400nm, about 1nm to about 300nm, about 1nm to about 200nm or about 1nm to about 100nm. Therefore, the terms "nanostructure", "nanoparticle" and "nanomaterial" etc. as used herein can include a structure with at least one size within the range not exceeding the range. The terms "nanostructure", "nanoparticle" and "nanomaterial" etc. as used herein can include a structure with at least one following size, the size being no more than about 100nm, no more than about 90nm, no more than about 80nm, no more than about 70nm, no more than about 60nm, no more than about 50nm, no more than about 40nm, no more than about 30nm, no more than about 20nm or no more than about 10nm.
[0053] The term "nanostructure" as used herein refers broadly to an arrangement of interconnected elements in a system having at least one dimension in the nanometer scale. The nanostructures described herein may include nanoparticles, nanorods, nanofibers, nanoneedles, nanoplates, and nanotubes, etc. When used in the context of nanoparticles, the term "size" may refer to the diameter of the nanoparticle, although it is not limited in itself.
[0054] The term "particle" as used herein refers broadly to a discrete entity or discrete body. The particles described herein may include organic, inorganic, composite particles or biological particles. The particles used herein may also be large particles formed by aggregates of multiple sub-particles or fragments of small objects. The particles of the present disclosure may be spherical, substantially spherical or non-spherical, such as irregularly shaped particles or ellipsoidal particles. When used to refer to particles, the term "size" broadly refers to the maximum dimension of the particle. For example, when the particle is substantially spherical, the term "size" may refer to the diameter of the particle; or when the particle is substantially non-spherical, the term "size" may refer to the maximum length of the particle.
[0055] Unless otherwise stated, the terms "coupled" or "connected" as used in this specification are intended to encompass direct connection or connection through more than one intermediate means.
[0056] As used herein, the term "associated with" when referring to two elements refers to a broad relationship between the two elements. Relationships include, but are not limited to, physical, chemical, or biological relationships. For example, when element A is associated with element B, elements A and B may be attached to each other directly or indirectly, or element A may contain element B, or vice versa.
[0057] When referring to two elements, the term “adjacent” used herein means that one element is very close to another element, and may be, but is not limited to, the two elements contacting each other, or may further include the elements being separated by one or more additional elements disposed therebetween.
[0058] The term "and / or", such as "X and / or Y", should be understood to mean "X and Y" or "X or Y", and should be considered to provide clear support for both meanings or either meaning.
[0059] Furthermore, in the description herein, whenever the word "substantially" is used, it is understood to include, but is not limited to, "entirely" and "completely", etc. Furthermore, whenever terms such as "comprising" and "comprise" are used, they are intended to be non-limiting descriptive language, as they broadly include the elements / components described after these terms, in addition to other components not explicitly described. For example, when "comprising" is used, a reference to "a" feature is also intended to be a reference to "at least one" of the feature. In appropriate contexts, terms such as "consisting" and "consisting of" can be considered as subsets of terms such as "comprising" and "comprise". Therefore, in the embodiments disclosed herein using terms such as "comprising" and "comprise", it should be understood that these embodiments provide teachings of corresponding embodiments using terms such as "consisting" and "consisting of". In addition, terms such as "about" and "approximately," whenever used, generally mean a reasonable variation, such as a variation of + / - 5% of a disclosed value, or a variation of 4% of a disclosed value, or a variation of 3% of a disclosed value, a variation of 2% of a disclosed value, or a variation of 1% of a disclosed value.
[0060] In addition, in the description herein, certain values may be disclosed within a range. The values showing the endpoints of a range are intended to illustrate a preferred range. Whenever a range has been described, the range is intended to cover and teach all possible subranges and each numerical value within the range. That is, the endpoints of a range should not be interpreted as inflexible limitations. For example, the description of a range of 1% to 5% is intended to have specifically disclosed subranges of 1% to 2%, 1% to 3%, 1% to 4%, 2% to 3%, etc., and individually, values within the range such as 1%, 2%, 3%, 4% and 5%. The above specifically disclosed intentions are applicable to any depth / width of a range.
[0061] In addition, when describing some embodiments, the present disclosure may have disclosed methods and / or processes as a specific order of steps. However, unless otherwise required, it should be understood that the method or process should not be limited to the disclosed specific order of steps. Other orders of steps are also possible. The specific order of steps disclosed herein should not be interpreted as an undue limitation. Unless otherwise required, the method and / or process disclosed herein should not be limited to the steps performed in a written order. The order of steps can be changed and still remain within the scope of the present disclosure.
[0062] Furthermore, it will be understood that although the present disclosure provides embodiments having one or more of the features / characteristics discussed herein, one or more of these features / characteristics may be abandoned in other alternative embodiments, and the present disclosure provides support for such abandoners and these relevant alternative embodiments.
[0063] It will also be understood that in case priority of an earlier application is claimed, the entire content of the earlier application is also deemed to form part of the present disclosure and can be used as support for the embodiments disclosed herein. DETAILED DESCRIPTION
[0064] Disclosed below are exemplary non-limiting embodiments of materials comprising geminal metal atom pairs supported on a support, catalysts comprising the materials, methods of preparing the materials, methods of catalyzing coupling reactions, and methods related thereto.
[0065] Material
[0066] A material is provided, which comprises geminal metal atom pairs. In various embodiments, the geminal metal atom pairs are stabilized / supported / anchored / attached / coordinated / connected / bonded / bound to a carrier / support within the material. In various embodiments, the geminal metal atom pairs are regularly or uniformly anchored / supported / distributed along / in therein / through the carrier / support. In various embodiments, the geminal metal atom pairs comprise single atom sites paired with specific coordination and spatial proximity. Advantageously, this unique structure / coordination / spatial proximity allows multiple geminal metal atom pairs to be incorporated and loaded on the carrier. Therefore, in various embodiments, the material comprises a high metal density. Even more advantageously, this unique structure / coordination / spatial proximity imparts catalytic properties to the material, making it desirable / attractive for the material to be used as a catalyst. In various embodiments, during catalysis, multiple geminal metal atom pairs act as adsorbents, advantageously enabling adsorption of a wide range of reactants / substrates (with multiple coordination sites and / or steric hindrance / dense / crowded structures) over / on the geminal metal atom pairs, and thus effectively activating such reactants / substrates. In various embodiments, multiple geminal metal atom pairs can adsorb and / or activate reactants / substrates of the same or different types. For example, a material can exhibit co-adsorption, wherein each geminal metal atom pair adsorbs two different reactants. In various embodiments, a material can adsorb more than two, three or four different reactants / substrates, and then activate the reactants / substrates.
[0067] In various embodiments, the material is substantially free of metal agglomerates and / or metal clusters. Advantageously, the presence of geminal metal atom pairs avoids the risk of a restricted spatial environment and / or limited ability to adsorb active reactants / substrates during catalysis, which otherwise may occur in the presence of metal agglomerates and / or metal clusters.
[0068] In various embodiments, each geminal metal atom pair comprises two single / monomeric / mononuclear metal atoms (e.g., M 1 and M 2 ). In various embodiments, two single / monomeric / mononuclear metal atoms are referred to as "geminal metal atom pairs", and refer to two single metal atoms attached to the same carrier / support. In various embodiments, the two single metal atoms in each geminal metal atom pair are not attached / coordinated / connected / bound to each other (e.g., chemically or physically). That is, in various embodiments, the two single metal atoms are separated / separated from each other (e.g., electronically separated / separated). However, it should be understood that, despite being electronically separated, in various embodiments, the two single / monomeric / mononuclear metal atoms interact with each other via geminal interactions / coupling.
[0069] In various embodiments, each geminal metal atom pair is substantially regularly / uniformly / evenly spaced from each other. In various embodiments, two single / monomeric / mononuclear metal atoms are substantially regularly / uniformly / evenly spaced from each other. In various embodiments, the average distance between each geminal metal atom pair (or between two single / monomeric / mononuclear metal atoms) is about to about about to about No more than about No more than about No more than about No more than about No more than about No more than about No more than about No more than about or not more than about For example, the distance between each geminal metal atom pair (or between two single / monomeric / mononuclear metal atoms / centers) may be about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about or about
[0070] In various embodiments, M 1 -M 2 or M 1 …M 2 The average distance is about to about about to about No more than about No more than about No more than about No more than about No more than about No more than about No more than about No more than about or not more than about For example, M 1 -M 2 or M 1 …M 2 The average value of the distance can be about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about about or about In various embodiments, two single metal atoms / centers are regularly / uniformly / evenly spaced apart, with a ground state separation of about 0.10 nm to about 1.0 nm, about 0.11 nm to about 0.9 nm, about 0.12 nm to about 0.8 nm, about 0.13 nm to about 0.7 nm, about 0.14 nm to about 0.6 nm, about 0.15 nm to about 0.5 nm, about 0.49 nm, about 0.48 nm, about 0.47 nm, about 0.46 nm, about 0.45 nm, about 0.44 nm, about 0.43 nm, about 0.42 nm, about 0.41 nm, about 0.40 nm, about 0.39 nm, about 0.38 nm, about 0.37 nm, about 0.36 nm, about 0.35 nm, about 0.34 nm, about 0.33 nm, about 0.32 nm, about 0.31 nm, or about 0.30 nm from each other. It should be understood that in various embodiments, the distance between two single metal atoms / centers depends on the support (e.g., the location of the metal coordination site in the support). Advantageously, a regular / uniform ground state separation imparts coordination dynamics to the material (i.e., dynamic / adaptive metal-metal coordination / coupling, such as bridge coupling of geminal metal atoms / centers), thereby achieving site synergy.
[0071] In various embodiments, the carrier / support comprises more than one atom, functional group, part and / or metal coordination site. In various embodiments, the atom, functional group, part and / or metal coordination site has no metal and / or substantially no metal. In various embodiments, the carrier comprises multiple atoms, functional groups, parts and / or metal coordination sites that are periodically and / or present in large quantities in / throughout the carrier. Multiple atoms, functional groups, parts and / or metal coordination sites can be regularly / uniformly / averagely spaced apart from each other in (in) / throughout the carrier. Advantageously, in various embodiments, multiple atoms, functional groups, parts and / or metal coordination sites in the carrier are designed to receive, coordinate, support and / or anchor geminal metal atom pairs with regular / ordered arrangement. Therefore, in various embodiments, the dynamic / adaptive coordination / coupling of geminal metal atoms (given by regular / uniform ground state separation) is attributed to the regular / ordered arrangement of metal coordination sites in the carrier. Advantageously, in various embodiments, the regular structure of the polymer support (eg, polymeric carbon nitride) allows / enables the formation of metal geminal sites via a simple ion exchange and activation process, which is maximized at high metal density.
[0072] In various embodiments, the two single metal atoms are each stabilized / loaded on / attached / coordinated / connected / bonded / bound to a different metal coordination site of the support. That is, in various embodiments, each single metal atom is designed to bridge and / or connect two different metal coordination sites in the support together. In various embodiments, each single metal atom is stabilized / loaded on / coordinated / connected / bonded / bound to two different metal coordination sites of the support in a diagonal or linear arrangement.
[0073] In various embodiments, the material comprises a structure represented by the general formula (1); and a structure represented by the general formula (2):
[0074] –A 1 -M 1 -A 2 -(1)
[0075] –A 3 -M 2 -A 4 -(2)
[0076] in
[0077] M 1 and M 2 Each is independently a single / monomeric / mononuclear metal atom;
[0078] M 1 and M 2 is a pair of geminal metal atoms; and
[0079] A 1 , A 2 , A 3 and A 4 Each is independently an atom, functional group, moiety or metal coordination site of a carrier / support.
[0080] A 1 , A 2 , A 3 and A 4 Can be independently selected from the group consisting of -C-, -N-, -P- and -S-. In various embodiments, A 1 , A 2 , A 3 and A 4 Each is independently -N-. For example, a material may contain -NM 1 -N-CONSTRUCT and / or -NM 2 -N- configuration. In various embodiments, the material comprises diagonally coordinated -NM 1 -N- configuration and / or diagonally coordinated -NM 2 -N-construction.
[0081] In various embodiments, the carrier is metal-free or substantially free of metal atoms / particles / ions. The carrier may comprise a nanocrystalline structure, such as a polycrystalline having at least one following size: the size is no more than about 100 nm, no more than about 90 nm, no more than about 80 nm, no more than about 70 nm, no more than about 60 nm, no more than about 50 nm, no more than about 40 nm, no more than about 30 nm, no more than about 20 nm, or no more than about 10 nm.
[0082] In various embodiments, the carrier comprises a polymer. Therefore, in various embodiments, the carrier is a polymer carrier. In various embodiments, the polymer carrier comprises a polymer (for example, an organic polymer) having more than one atom selected from carbon, nitrogen, phosphorus, sulfur (sulfur / sulphur) or hydrogen etc. or its combination. In various embodiments, the polymer carrier is an organic polymer containing carbon / carbonyl, nitrogen / nitrogen-based, phosphorus / phosphorus-based and / or containing sulfur (sulfur / sulphur) / sulfur (sulfur / sulphur) base. For example, the polymer carrier can be an organic polymer containing CC / CC base, containing CN / CN base, containing CP / CP base and / or containing CS / CS base. Advantageously, in various embodiments, the use of nanocrystal polymer carriers (for example, polymeric carbon nitride) allows accurate control of the proximity of metal centers.
[0083] In various embodiments, the polymer carrier comprises more than one layer / sheet, or is derived therefrom. In various embodiments, the polymer carrier is in the form of a layered structure. That is, in various embodiments, the polymer carrier is designed to include a polymer chain containing a fused nitrogen-containing heterocycle, and the fused nitrogen-containing heterocycle is assembled to form a layer / sheet. The fused nitrogen-containing heterocycle can be a fused triazine ring (e.g., 1,3,5-triazine ring). In various embodiments, the carrier comprises a polymer chain of more than two fused triazine rings, for example, the carrier / support may include a polymer chain with two fused triazine rings, a polymer chain with three fused triazine rings (e.g., heptazine), a polymer chain with four fused triazine rings, or a polymer chain with five fused triazine rings. Therefore, in various embodiments, the polymer carrier comprises a nitrogen-rich polymer (e.g., carbon nitride polymer or polymerized carbon nitride (PCN)) or a derivative thereof. Advantageously, the layers / sheets of polymer chains bonded to each other or held together by van der Waals forces contribute to imparting strength and stability to the polymer carrier, allowing the carrier to provide / serve as a support for the material. Even more advantageously, the entire two-dimensional (2D) organo-metal lattice structure (eg, 2D nanosheets) of the polymer support provides higher / larger surface area and reduced diffusion paths for charges to the material, thus enhancing the catalytic performance / properties of the material.
[0084] In various embodiments, the material is suitable for exfoliation or is capable of exfoliation into atomically thin nanostructures.The material may be provided in the form of exfoliated nanostructures.
[0085] In various embodiments, the material has a nanostructure comprising one or more of the following shapes / structures: nanoflakes, nanosheets, nanolayers, nanoplates, nanorods, nanofibers, nanoneedles, and nanotubes.
[0086] In various embodiments, the total number of metal atoms present in the material is an even number. For example, the total number of metal atoms present in the material can be at least about 2, at least about 4, at least about 6, at least about 8, at least about 10, at least about 12, at least about 14, at least about 16, at least about 18, at least about 20, at least about 22, at least about 24, at least about 26, at least about 28, at least about 30, at least about 32, at least about 34, at least about 36, at least about 38, at least about 40, at least about 42, at least about 44, at least about 46, at least about 48, at least about 50, at least about 60, at least about 70, at least about 80, at least about 90, at least about 100, at least about 150, or at least about 160. , at least about 200, at least about 250, at least about 300, at least about 350, at least about 400, at least about 450, at least about 500, at least about 550, at least about 600, at least about 650, at least about 700, at least about 750, at least about 800, at least about 850, at least about 900, at least about 950, at least about 1,000, at least about 2,000, at least about 3,000, at least about 4,000, at least about 5,000, at least about 6,000, at least about 7,000, at least about 8,000, at least about 9,000, or at least about 10,000.
[0087] In various embodiments, the material comprises a high metal density / concentration (due to the presence of multiple geminal metal atom pairs). In various embodiments, the material comprises about 0.1 wt% to about 50.0 wt%, about 0.15 wt% to about 47.5 wt%, about 0.2 wt% to about 45.0 wt%, about 0.35 wt% to about 42.5 wt%, about 0.5 wt% to about 40.0 wt%, about 0.75 wt% to about 37.5 wt%, about 1.0 wt% to about 35.0 wt%, about 1.5 wt% to about 32.5 wt%, about 2.0 wt% to about 30.0 wt%, about 3.5 wt% to about 27.5 wt%, about 5.0 wt% to about 25.0 wt%, about 7.5 wt% to about 22.5 wt%, about 10.0 wt% to about 20.0 wt%, about 12.5 wt% to about 17.5 wt%, or about 15.0 wt% of the metal.
[0088] In various embodiments, the metal comprises a transition metal. For example, the metal atom can be a transition metal atom selected from the group consisting of copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), iron (Fe), manganese (Mn), chromium (Cr), vanadium (V), titanium (Ti), scandium (Sc), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), lanthanum (La), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), gold (Au), mercury (Hg), actinium (Ac), and combinations thereof.
[0089] In various embodiments, the metal is low-valent. That is, in various embodiments, the metal can have a low valence / valence of 1 or 2 or have a valence state / oxidation number / charge of +1 or +2. For example, the metal can be a low-valent (e.g., monovalent or divalent) metal such as Cu(I), Pd(I), Ag(I), Zn(II), Au(I), Ni(II), Co(II), Fe(II), Mn(II), Cr(II), V(II), Ti(II), Sc(II), Y(II), Zr(II), Nb(II), Mo(II), Tc(II), Ru(II), Rh(II), Cd(II), La(II), Hf(II), Ta(II), W(II), Re(II), Os(II), Ir(II), Pt(II), Hg(II) and Ac(II). Advantageously, the low valence (ie, monovalent) of the activated metal center enhances the catalytic performance / properties of the material by lowering the activation barrier and facilitating the activation of reactants / substrates during catalysis.
[0090] In various embodiments, the material comprises a first / inner shell comprising a single / monomeric / mononuclear metal atom and a first atom of the carrier / support. In various embodiments, the interatomic distance between the single / monomeric / mononuclear metal atom in the first shell and the first atom of the carrier / support is about to about about to about about to about about to about about to about about to about about to about about to about about to about about to about about to about about to about about to about or about to about
[0091] In various embodiments, the material comprises a second / outer shell comprising a single / monomeric / mononuclear metal atom and a second atom of the carrier / support. In various embodiments, the interatomic distance between the single / monomeric / mononuclear metal atom in the second shell and the second atom of the carrier / support is about to about about to about about to about about to about about to about about to about about to about about to about about to about or about to about
[0092] In various embodiments, the material, geminal metal atom and / or single metal atom comprises one or more catalytically active sites and / or is capable of being used as one or more catalytically active sites. In various embodiments, the active sites are different from the prior art in the art. Embodiments of the material comprise two metal atom sites (composed of pairs of regularly separated low valence single metal atom sites), which is completely different from the prior art involving single metal atom sites.
[0093] In various embodiments, the material is suitable for use as a catalyst or suitable for catalysis. In various embodiments, a library of heterogeneous catalyst materials comprising multiple pairs of geminal metal atoms is provided, the geminal atoms being stabilized / supported / coordinated / connected / bonded / bound to a carrier / support. Thus, the material may also be referred to as a "geminal catalyst", "solid-state catalyst", "solid-state catalyst material" and / or "compound".
[0094] In various embodiments, catalyst comprises heterogeneous catalyst.That is, in various embodiments, catalyst exists with the phase different from reaction mixture.For example, catalyst can be solid form (or exist with solid phase), and reaction mixture can be liquid form (or exist with liquid phase).Advantageously, the use of heterogeneous catalyst allows the recycling, reuse and / or recovery of material, and its performance (such as efficiency) and / or metal leaching in environment do not change substantially.Therefore, in various embodiments, compared with the catalyst with higher metal leaching tendency in the art, the material is substantially safer, less toxic or nontoxic, greener, environmentally friendly / benign and / or has the environmental footprint of reduction.In various embodiments, material is durable, stable and / or recyclable / reusable / recoverable.Material can be recycled / reused / recovered after at least 1 time, at least 2 times, at least 3 times, at least 4 times, at least 5 times, at least 6 times, at least 7 times, at least 8 times, at least 9 times, at least 10 times, at least 15 times, at least 20 times, at least 25 times or at least 30 reaction cycles / uses. In various embodiments, the material is recyclable / reusable / recoverable after the above number of times without substantial loss of catalytic properties. In various embodiments, the material is recycled / reused / recovered by washing with an aqueous medium (eg, deionized water).
[0095] Advantageously, in various embodiments, the material is easily separated from the product after catalysis, which significantly reduces operating costs and ensures the quality of the product (eg, the resulting drug).
[0096] In various embodiments, the material, geminal metal atom and / or single / monomeric / mononuclear metal atom is capable of catalyzing a coupling reaction having an activation barrier of about 0.25 eV, about 0.20 eV, about 0.19 eV, about 0.18 eV, about 0.17 eV, about 0.16 eV, about 0.15 eV, or about 0.10 eV. Advantageously, in various embodiments, the activation barrier is no more than about 0.50 eV, no more than about 0.40 eV, no more than about 0.30 eV, no more than about 0.25 eV, no more than about 0.20 eV, no more than about 0.15 eV, or no more than about 0.10 eV.
[0097] In various embodiments, the material, geminal metal atom and / or single metal atom can catalyze the coupling reaction. In various embodiments, the coupling reaction involves a wide range of reactants / substrates, including but not limited to heteroaryl halides (e.g., heteroaryl iodides, heteroaryl bromides, heteroaryl chlorides), aryl halides (e.g., aryl iodides, aryl bromides, aryl chlorides), reactants / substrates containing one or more hydroxyl groups, reactants / substrates containing one or more amino groups, reactants / substrates containing one or more amide groups, reactants / substrates containing one or more sulfonamide groups, reactants / substrates containing one or more alkynyl groups, reactants / substrates containing one or more thiol groups, ...sulfonamide groups, reactants / substrates containing one or more alkynyl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrates containing one or more sulfhydryl groups, reactants / substrat Electron / electron-poor aromatic reactants / substrates, alcohols, halogenated alcohols (e.g., fluorinated alcohols), deuterated alcohols (e.g., deuterated methanol), heterocyclic compounds (e.g., imidazoles, pyrazoles, triazoles), alkynes, thiols (e.g., alkylthiols (thiol / mercaptan) or thiophenol), azides (e.g., alkyl azides, aryl azides), acetylenes (e.g., alkyl acetylene, aryl acetylene), L-menthol, DL-menthol, stigmasterol, DL-isoborneol, galactose, 1,2,3,4-diacetone galactose, testosterone, prednisolone, derivatives thereof, etc., and combinations thereof.
[0098] In various embodiments, the coupling reaction comprises a cross-coupling reaction, a cross-coupling bond formation, a cycloaddition such as an azide-alkyne cycloaddition, a carbon-carbon bond formation (i.e., a CC coupling), a carbon-heteroatom bond formation (e.g., a CN coupling, a CO coupling, a CS coupling, etc.), an N-arylation, the like, and combinations thereof.
[0099] Catalytic method
[0100] A method for catalyzing a coupling reaction is provided, the method comprising:
[0101] (ai) providing materials as disclosed herein; and
[0102] (a-ii) mixing the material with two or more reactants / substrates to be coupled under appropriate conditions to obtain a coupling product.
[0103] In various embodiments, the catalytic method includes heterogeneous catalysis. For example, the catalytic method includes using a material (in solid form) placed in a reaction mixture (in liquid form).
[0104] In various embodiments, the step of providing the material includes adding the material to the anhydrous solvent system under vacuum, in an inert atmosphere (e.g., in the presence of an inert gas such as argon or nitrogen) or in the absence of a reactive gas such as oxygen (e.g., dissolved oxygen). The purge of the inert gas maintains the oxygen-free system throughout the reaction process / continuation / cycle, and it should be understood that various inert gases can be used in the embodiments of the methods disclosed herein. In various embodiments, the anhydrous solvent system comprises an anhydrous or dry solvent selected from the group consisting of formamide / methanamide, dimethylformamide (DMF), dimethyl sulfoxide (DMSO), dioxane (e.g., 1,4-dioxane) and acetonitrile, etc., and combinations / mixtures thereof.
[0105] In various embodiments, the step of providing a material comprises adding the material to an aqueous solvent system under ambient conditions. For example, the material can be added to an aqueous solvent system at ambient temperature and / or pressure. In various embodiments, the aqueous solvent system comprises an aqueous solvent selected from the group consisting of pentanol, butanol, cyclohexanol, octanol, propanol, heptanol, hexanol, acetylacetone, ethyl acetoacetate, benzyl alcohol, acetic acid, aminoethanol, ethanol, diethylene glycol, methanol, ethylene glycol, and water, and the like, and combinations / mixtures thereof.
[0106] In various embodiments, any solvent that is effective as a medium for components (e.g., materials, reactants / substrates) comprising the reaction mixture can be used in the embodiments disclosed herein. In various embodiments, the solvent is capable of substantially dissolving the components present in the reaction mixture. The solvent can be selected from the group consisting of: formamide / methanamide, dimethylformamide (DMF), dimethyl sulfoxide (DMSO), dioxane (e.g., 1,4-dioxane), acetonitrile, pentanol, butanol, cyclohexanol, octanol, propanol, heptanol, hexanol, acetylacetone, ethyl acetoacetate, benzyl alcohol, acetic acid, aminoethanol, ethanol, diethylene glycol, methanol, ethylene glycol and water, etc., and mixtures / combinations thereof.
[0107] In various embodiments, the step of providing a material comprises adding the material to a base. In various embodiments, the base is an inorganic base or an organic base. The base can be an inorganic base selected from the group consisting of metal tert-butoxides, metal phosphates, metal carbonates, metal bicarbonates, metal hydroxides, metal hydrides, and mixtures thereof. For example, the base can be lithium tert-butoxide (LiOtBu), sodium tert-butoxide (NaOtBu), potassium tert-butoxide (KOtBu), lithium phosphate (Li 3 PO 4 ), sodium phosphate (Na 3 PO4 ), tripotassium phosphate (K 3 PO 4 )、Lithium carbonate (Li 2 CO 3 ), sodium carbonate (Na 2 CO 3 ), potassium carbonate (K 2 CO 3 ), cesium carbonate (Cs 2 CO 3 ), sodium bicarbonate (NaHCO 3 ), sodium hydroxide (NaOH), potassium hydroxide (KOH) and cesium hydroxide (CsOH), etc., and combinations / mixtures thereof.
[0108] In various embodiments, the step of providing a material comprises adding the material in an amount of about 0.1 mol% to about 50.0 mol%, about 0.2 mol% to about 45.0 mol%, about 0.35 mol% to about 42.5 mol%, about 0.5 mol% to about 40.0 mol%, about 0.6 mol% to about 39.0 mol%, about 0.7 mol% to about 38.0 mol%, about 0.8 mol% to about 37.0 mol%, about 0.9 mol% to about 36.0 mol%, about 1.0 mol% to about 35.0 mol%, about 1.2 mol% to about 34.0 mol%, about 1 %. .4 mol % to about 33.0 mol %, about 1.6 mol % to about 32.0 mol %, about 1.8 mol % to about 31.0 mol %, about 2.0 mol % to about 30.0 mol %, about 3.5 mol % to about 32.5 mol %, about 5.0 mol % to about 25.0 mol %, about 10.0 mol % to about 20.0 mol %, about 11.0 mol % to about 19.0 mol %, about 12.0 mol % to about 18.0 mol %, about 13.0 mol % to about 17.0 mol %, about 14.0 mol %, about 15.0 mol % or about 16.0 mol %.
[0109] In various embodiments, the coupling reaction involves a wide range of reactants / substrates, including but not limited to heteroaryl halides (e.g., heteroaryl iodides, heteroaryl bromides, heteroaryl chlorides), aryl halides (e.g., aryl iodides, aryl bromides, aryl chlorides), reactants / substrates containing one or more hydroxyl groups, reactants / substrates containing one or more amino groups, reactants / substrates containing one or more amide groups, reactants / substrates containing one or more sulfonamide groups, reactants / substrates containing one or more alkynyl groups, reactants / substrates containing one or more thiol groups, ... Electron / electron-poor aromatic reactants / substrates, alcohols, halogenated alcohols (e.g., fluorinated alcohols), deuterated alcohols (e.g., deuterated methanol), heterocyclic compounds (e.g., imidazoles, pyrazoles, triazoles), alkynes, thiols (e.g., alkylthiols (thiol / mercaptan) or thiophenol), azides (e.g., alkyl azides, aryl azides), acetylenes (e.g., alkyl acetylene, aryl acetylene), L-menthol, DL-menthol, stigmasterol, DL-isoborneol, galactose, 1,2,3,4-diacetone galactose, testosterone, prednisolone, derivatives thereof, etc., and combinations thereof.
[0110] In various embodiments, the coupling reaction comprises a cross-coupling reaction, a cross-coupling bond formation, a cycloaddition such as an azide-alkyne cycloaddition, a carbon-carbon bond formation (i.e., a C-C coupling), a carbon-heteroatom bond formation (e.g., a CN coupling, a CO coupling, a CS coupling, etc.), an N-arylation, the like, and combinations thereof.
[0111] In various embodiments, the coupling reaction comprises the following reaction:
[0112]
[0113] in
[0114] A is an optionally substituted monocyclic or polycyclic hydrocarbon ring system having 5 to 42 ring atoms, wherein up to 3 C atoms in each ring are optionally substituted by heteroatoms independently selected from the group consisting of O, N, S and NH, and wherein the ring system comprises a 4-membered ring, a 5-membered ring, a 6-membered ring, and / or mixtures thereof;
[0115] X is a halogen selected from the group consisting of F, Cl, Br and I;
[0116] Y is selected from the group consisting of O, N, C and S, and
[0117] wherein Y forms part of the organic compound / nucleophile.
[0118] In various embodiments, A comprises an aromatic and / or heteroaromatic group selected from the group consisting of benzene, naphthalene, indene, anthracene, phenanthrene, fluorene, furan, thiophene, pyrrole, pyrazole, imidazole, oxazole, thiazole, triazole, oxadiazole, thiadiazole, tetrazole, benzodioxole (e.g., 1,3-benzodioxole), benzofuran, benzothiophene, benzopyrrole, benzodifuran, benzodithiophene, benzodipyrrole, dibenzofuran, dibenzothiophene, dibenzopyrrole / carbazole, pyrrolidine ... pyridine, benzopyridine (e.g., isoquinoline and quinoline), bipyridine (e.g., 2,2'-bipyridine, 4,4'-bipyridine, 3,4'-bipyridine), pyridazine (1,2-diazine), bipyridazine (e.g., 3,3'-bipyridazine), pyrimidine (1,3-diazine), bipyrimidine (e.g., 2,2'-bipyrimidine), pyrazine (1,4-diazine), triazine (e.g., 1,2,3-triazine, 1,2,4-triazine and 1,3,5-triazine), phenanthroline, quinoxaline, phenazine or acridine, etc., or a combination thereof.
[0119] In various embodiments, when Y is O, the organic compound / nucleophile containing Y is an alcohol. In various embodiments, the organic compound / nucleophile containing Y is a haloalcohol (e.g., a fluorinated alcohol). In various embodiments, the organic compound / nucleophile containing Y is a deuterated alcohol (e.g., deuterated methanol).
[0120] In various embodiments, when Y is N, the organic compound / nucleophile containing Y is a nitrogen-based nucleophile (e.g., a nitrogen-containing heterocyclic compound (e.g., imidazole, pyrazole, triazole), an amine (e.g., an arylamine, an alkylamine), a cyclic amine, an amide, a cyclic amide (or lactam), a sulfonamide, a cyclic sulfonamide (or sulfam)).
[0121] In various embodiments, when Y is C, the organic compound / nucleophile containing Y is an alkyne (eg, a terminal alkyne). In various embodiments, when Y is C, the organic compound / nucleophile containing Y is an electron-poor (hetero)arene.
[0122] In various embodiments, when Y is S, the organic compound / nucleophile containing Y is a thiol (eg, a thiol / mercaptan or thiophenol).
[0123] In various embodiments, one or more hydrogen atoms in A and / or one or more hydrogen atoms in the organic compound / nucleophile containing Y are replaced by chemical moieties or functional groups, such as alcohol, fluoroalcohol, alkoxy (e.g., methoxy, ethoxy), alkanoyloxy, alkoxycarbonyl, alkenyl, alkyl (e.g., methyl, ethyl, propyl, tert-butyl), alkynyl, alkylcarbonyloxy (-OC(O)alkyl), amide (-C(O)NH-alkyl- or -alkylNHC(O)alkyl), amino / amine (e.g., alkylamino, arylamino, arylalkylamino), aryl, aryloxy, azo, carbamoyl (-NHC(O)O-alkyl- or -OC(O)NH-alkyl), carbamyl (e.g., CONH 2 , CONH-alkyl, CONH-aryl, and CONH-arylalkyl), carboxyl, carboxylic acid, cyano, ester (e.g., acetate), ether (e.g., methoxy, ethoxy), halide, haloalkyl (e.g., -CCl 3 , -CF 3 ,-C(CF 3 ) 3 ), heteroalkyl, isocyanate, isothiocyanate, nitrile, nitro, phosphodiester, sulfide, sulfonamide (e.g. SO 2 NH 2 ), sulfone, sulfonyl (e.g., alkylsulfonyl, arylsulfonyl and arylalkylsulfonyl), sulfoxide, thiol (e.g., mercapto, thioether), urea or tosyl.
[0124] In various embodiments, the coupling reaction comprises the following reaction:
[0125]
[0126] in
[0127] Ring (Het)Ar contains optionally substituted aryl (ie, Ar) and / or heteroaryl (ie, HetAr).
[0128] In various embodiments, (Het)Ar comprises an optionally substituted aromatic and / or heteroaromatic group selected from the group consisting of benzene, naphthalene, indene, anthracene, phenanthrene, fluorene, furan, thiophene, pyrrole, pyrazole, imidazole, oxazole, thiazole, triazole, oxadiazole, thiadiazole, tetrazole, benzodioxole (e.g., 1,3-benzodioxole), benzofuran, benzothiophene, benzopyrrole, benzodifuran, benzodithiophene, benzodipyrrole, dibenzofuran, dibenzothiophene, dibenzopyrrole / carbazole, pyridine. , benzopyridine (e.g., isoquinoline and quinoline), bipyridine (e.g., 2,2'-bipyridine, 4,4'-bipyridine, 3,4'-bipyridine), pyridazine (1,2-diazine), bipyridazine (e.g., 3,3'-bipyridazine), pyrimidine (1,3-diazine), bipyrimidine (e.g., 2,2'-bipyrimidine), pyrazine (1,4-diazine), triazine (e.g., 1,2,3-triazine, 1,2,4-triazine and 1,3,5-triazine), phenanthroline, quinoxaline, phenazine or acridine, etc., or a combination thereof.
[0129] In various embodiments, the catalytic process achieves a yield (of the coupled product) of at least about 50.0%, at least about 55.0%, at least about 60.0%, at least about 65.0%, at least about 70.0%, at least about 75.0%, at least about 80.0%, at least about 81.0%, at least about 82.0%, at least about 83.0%, at least about 84.0%, at least about 85.0%, at least about 86.0%, at least about 87.0%, at least about 88.0%, at least about 89.0% , at least about 90.0%, at least about 91.0%, at least about 92.0%, at least about 93.0%, at least about 94.0%, at least about 95.0%, at least about 96.0%, at least about 97.0%, at least about 98.0%, at least about 99.0%, at least about 99.1%, at least about 99.2%, at least about 99.3%, at least about 99.4%, at least about 99.5%, at least about 99.6%, at least about 99.7%, at least about 99.8% or at least about 99.9%.
[0130] In various embodiments, the catalytic process achieves a conversion (of the coupled product) of at least about 50.0%, at least about 55.0%, at least about 60.0%, at least about 65.0%, at least about 70.0%, at least about 75.0%, at least about 80.0%, at least about 81.0%, at least about 82.0%, at least about 83.0%, at least about 84.0%, at least about 85.0%, at least about 86.0%, at least about 87.0%, at least about 88.0%, at least about 89.0% , at least about 90.0%, at least about 91.0%, at least about 92.0%, at least about 93.0%, at least about 94.0%, at least about 95.0%, at least about 96.0%, at least about 97.0%, at least about 98.0%, at least about 99.0%, at least about 99.1%, at least about 99.2%, at least about 99.3%, at least about 99.4%, at least about 99.5%, at least about 99.6%, at least about 99.7%, at least about 99.8% or at least about 99.9%.
[0131] In various embodiments, the catalytic process achieves a selectivity or regioselectivity (of the coupled products) of at least about 50.0%, at least about 55.0%, at least about 60.0%, at least about 65.0%, at least about 70.0%, at least about 75.0%, at least about 80.0%, at least about 81.0%, at least about 82.0%, at least about 83.0%, at least about 84.0%, at least about 85.0%, at least about 86.0%, at least about 87.0%, at least about 88.0%, at least about 89.0%, at least about 90.0%, at least about 91.0%, at least about 92.0%, at least about 93.0%, at least about 94.0%, at least about 95.0%, at least about 96.0%, at least about 97.0%, at least about 98.0%, at least about 99.0%, at least about 100.0%, at least about 101.0%, at least about 102.0%, at least about 103.0%, at least about 104.0%, at least about 105.0%, at least about 106.0%, at least about 107.0%, at least about 108.0%, at least about 109.0%, at least about 110.0%, at least about 111.0%, at least about 112.0%, at least about 113.0%, at least about 114.0%, .0%, at least about 90.0%, at least about 91.0%, at least about 92.0%, at least about 93.0%, at least about 94.0%, at least about 95.0%, at least about 96.0%, at least about 97.0%, at least about 98.0%, at least about 99.0%, at least about 99.1%, at least about 99.2%, at least about 99.3%, at least about 99.4%, at least about 99.5%, at least about 99.6%, at least about 99.7%, at least about 99.8% or at least about 99.9%.
[0132] In various embodiments, the catalytic process achieves a turnover number (TON) of at least about 50, at least about 100, at least about 250, at least about 500, at least about 1,000, at least about 2,500, at least about 5,000, at least about 6,000, at least about 7,000, at least about 8,000, at least about 9,000, at least about 10,000, at least about 15,000, or at least about 20,000.
[0133] In various embodiments, the method includes catalyzing two or more different reactions simultaneously.
[0134] In various embodiments, the two single / monomeric / mononuclear metal atoms (e.g., M 1 and M 2 ) can switch from a first state in which they are not coordinated / connected / bonded to each other (e.g. before catalysis or after catalysis, when the product is desorbed / released) to a second state in which they are coordinated / connected / bonded to each other (during catalysis).
[0135] In various embodiments, the catalytic method includes catalyzing geminal atom-catalyzed organic cross-coupling reactions, which are different from other photocatalytic reactions such as photocatalytic CO 2 reduction, photocatalytic methane conversion and / or photocatalytic H 2 Precipitation.
[0136] Material preparation method
[0137] In various embodiments, there is provided a method for preparing a material as disclosed herein, the method comprising:
[0138] (i) reacting a metal precursor / metal source with a carrier / support disclosed herein to obtain / precipitate the material; and
[0139] (ii) separating said material.
[0140] In various embodiments, the reaction step is carried out in the presence of a solvent. For example, the reaction step may include mixing a metal precursor / metal source with a carrier / support in the presence of a solvent to obtain a composition. In the embodiments of the composition disclosed herein, any solvent that is effectively used as a medium for a component (e.g., a metal precursor / metal source, a carrier / support) comprising the composition can be used. In various embodiments, the solvent can substantially dissolve the components present in the composition. The solvent may include a polar solvent and / or a water-soluble solvent. In various embodiments, the solvent is selected from the group consisting of: formamide (formamide / methanamide), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), acetonitrile, amyl alcohol, butanol, cyclohexanol, octanol, propanol, heptanol, hexanol, acetylacetone, ethyl acetoacetate, benzyl alcohol, acetic acid, aminoethanol, ethanol, diethylene glycol, methanol, ethylene glycol and water, etc., and combinations / mixtures thereof. It should be understood that the type of solvent used depends on the type of metal precursor / metal source and carrier / support used, and is not limited to the above.
[0141] In various embodiments, the reacting step is performed at a temperature of about 20° C. to about 150° C., about 25° C. to about 145° C., about 30° C. to about 140° C., about 35° C. to about 135° C., about 40° C. to about 130° C., about 45° C. to about 125° C., about 50° C. to about 120° C., about 55° C. to about 115° C., about 60° C. to about 110° C., about 65° C. to about 105° C., about 70° C. to about 100° C., about 75° C. to about 95° C., about 80° C. to about 90° C., or about 85° C. For example, the reacting step can be performed at room temperature of about 20° C. to about 40° C. and then at an elevated temperature of about 90° C. to about 150° C.
[0142] In various embodiments, the reacting step is performed for a duration of about 5 minutes to about 48 hours, about 10 minutes to about 36 hours, about 15 minutes to about 24 hours, about 20 minutes to about 12 hours, about 25 minutes to about 11 hours, about 30 minutes to about 10 hours, about 1 hour to about 9 hours, about 2 hours to about 8 hours, about 3 hours to about 7 hours, about 4 hours to about 6 hours, or about 5 hours.
[0143] In various embodiments, the reacting step includes one or more of the steps of dispersing, mixing, stirring, sonicating, and / or ultrasonicating the mixture of the metal precursor / metal source and the carrier / support.
[0144] In various embodiments, the separation step includes one or more of the following steps: purifying, centrifuging, quenching and / or washing the material to remove impurities such as excess / free metal precursors and / or carriers / supports. The steps of purifying, centrifuging, quenching and / or washing can be repeated at least 1 time, at least 2 times, at least 3 times, at least 4 times, at least 5 times, at least 6 times, at least 7 times, at least 8 times, at least 9 times, at least 10 times, at least 15 times, at least 20 times with a washing medium. The washing medium can be an alcohol (e.g., ethanol, isopropanol). The washing medium can be an alcohol (e.g., ethanol, isopropanol).
[0145] In various embodiments, the method further includes one or more of the following post-reaction steps: optionally drying and / or heating the material under vacuum or in an inert atmosphere. The drying and / or heating step can be carried out in the presence of an inert gas such as argon or nitrogen. The drying and / or heating step can be carried out at a temperature of about 50°C to about 600°C, about 55°C to about 550°C, about 60°C to about 500°C, about 65°C to about 450°C, about 75°C to about 400°C, about 80°C to about 350°C, about 85°C to about 300°C, about 90°C to about 250°C, about 95°C to about 225°C, about 100°C to about 200°C, about 110°C to about 190°C, about 120°C to about 180°C, about 130°C to about 170°C, about 140°C to about 160°C or about 150°C. The drying and / or heating steps may be performed for a duration of about 1 hour to about 24 hours, about 2 hours to about 22 hours, about 3 hours to about 20 hours, about 4 hours to about 18 hours, about 5 hours to about 16 hours, about 6 hours to about 14 hours, about 7 hours to about 12 hours, or about 8 hours to about 10 hours, or about 9 hours.
[0146] In various embodiments, the method further includes the step of stripping the material and / or the carrier / support into an atomically thin nanostructure. For example, before being used as a catalyst, the material can be stripped via sonication, mechanical, thermal, hydrothermal, electrochemical, laser-assisted and / or microwave-assisted methods. For example, the carrier / support can be stripped via sonication, mechanical, thermal, hydrothermal, electrochemical, laser-assisted and / or microwave-assisted methods before reacting with a metal precursor / metal source to form a material.
[0147] In various embodiments, the metal precursor / metal source comprises a salt. In various embodiments, the metal precursor / metal source / metal salt comprises a metal chloride, a metal fluoride, a metal bromide, a metal iodide, a metal oxide, a metal sulfate, a metal sulfide, a metal cyanide, a metal thiocyanate, a metal acetylide, a metal acetate, a metal hydroxide, a metal hydride, a metal nitrate, a metal phosphide, a metal phosphate, a metal carbonate, a metal carbonate hydroxide, a metal chlorate, a metal arsenate, a metal azide, a metal acetylacetonate, a metal perchlorate, a metal triflate, a metal tetrafluoroborate, a metal benzoate, a metal chromite, a metal peroxide, and the like, and combinations thereof.
[0148] In various embodiments, the metal precursor / metal source / metal salt comprises a divalent metal cation. In various embodiments, the metal precursor / metal source / metal salt comprises a copper salt selected from the group consisting of: copper chloride (e.g., CuCl 2 ), copper fluoride (such as CuF 2 ), copper bromide (such as CuBr 2), copper iodide (such as CuI 2 ), copper oxide (such as CuO), copper sulfate (such as CuSO 4 ), copper sulfide (such as CuS), copper cyanide (such as CuCN 2 ), copper thiocyanate (such as Cu(SCN) 2 ), acetylene copper (such as Cu 2 C 2 ), copper acetate (e.g. Cu(OAc) 2 ), copper hydroxide (such as Cu(OH) 2 ), copper hydride (such as CuH 2 ), copper nitrate (e.g. Cu(NO 3 ) 2 ), copper phosphide (such as Cu 3 P), copper phosphate (such as Cu 3 (PO 4 ) 2 ), copper carbonate (such as CuCO 3 ), copper hydroxide carbonate (such as CuCO 3 (OH) 2 ), copper chlorate (e.g. Cu(ClO 3 ) 2 ), copper arsenate (such as Cu 3 (AsO 4 ) 2 ), copper azide (e.g. Cu(N 3 ) 2 ), copper acetylacetonate (e.g. Cu(O 2 C 5 H 7 ) 2 ), copper perchlorate (e.g. Cu(ClO 4 ) 2 ), copper trifluoromethanesulfonate (e.g. Cu(OSO 2 CF 3 ) 2 ), copper tetrafluoroborate (e.g. Cu(BF 4 ) 2 ), copper benzoate (e.g. Cu(C 6 H 5 CO 2 ) 2 ), copper chromite (such as Cu 2 Cr 2 O 5 ) and copper peroxide (such as CuO 2 ), etc., and combinations thereof.
[0149] In various embodiments, the reacting step includes adding / incorporating about 0.1 wt % to about 50.0 wt %, about 0.2 wt % to about 45.0 wt %, about 0.5 wt % to about 40.0 wt %, about 1.0 wt % to about 35.0 wt %, about 2.0 wt % to about 30.0 wt %, about 5.0 wt % to about 25.0 wt %, about 10.0 wt % to about 20.0 wt %, or about 15.0 wt % of a metal precursor / metal source.
[0150] In various embodiments, the reacting step includes adding / incorporating about 50.0 wt % to about 99.9 wt %, about 55.0 wt % to about 99.8 wt %, about 60.0 wt % to about 99.5 wt %, about 65.0 wt % to about 99.0 wt %, about 70.0 wt % to about 98.0 wt %, about 75.0 wt % to about 95.0 wt %, about 80.0 wt % to about 90.0 wt %, or about 85.0 wt % of the carrier / support.
[0151] In various embodiments, the material is formed / obtained via an ion exchange process, wherein the ions / atoms of the carrier / support are replaced by the ions / atoms of the metal precursor. For example, ions (metal coordination sites attached to the carrier / support) can be replaced by cations of the metal precursor.
[0152] In various embodiments, the materials / catalysts are prepared by post-synthetic methods, whereby the metal is introduced via an ion exchange strategy that allows the metal to be anchored on the surface of the support (e.g., polymeric carbon nitride). Advantageously, embodiments of the methods of the present disclosure are not compatible with direct synthesis methods of the art such as pyrolysis, where most of the metal is embedded in the bulk of the structure and remains inaccessible.
[0153] In various embodiments, the materials prepared by the embodiments of the methods disclosed herein realize a synergistic bridging pathway for a wide range of cross-coupling reactions, with significant activity, selectivity and stability, superior to all Cu nanocatalysts known to date, and even improved regioselectivity compared to benchmark homogeneous cuprous iodide catalysis. In various embodiments, compared to commonly used homogeneous catalytic systems (e.g., CuI), the materials prepared by the embodiments of the methods disclosed herein show much better catalytic activity and / or recyclability in a wide range of cross-coupling reactions. In various embodiments, the materials prepared by the embodiments of the methods disclosed herein also show a wide substrate range and / or a long operating life, stable recyclability, which is unmatched by homogeneous metal (e.g., Cu) catalysts.
[0154] The embodiment of the method is easy to implement, has low production cost (i.e. cost is effective), and can be carried out as a one-step direct synthesis method / one-pot synthesis method of pharmaceutical compounds. The embodiment of the method can also be used for the synthesis of biologically related compounds and be converted into continuous flow synthesis to produce complex molecules. Advantageously, the embodiment of the method is also environmentally benign, nontoxic and / or has substantially high scalability.
[0155] In various embodiments, the materials prepared by the embodiments of the methods disclosed herein include one or more of the following features or properties: wide applicability (e.g., suitable for most metal-catalyzed organic reactions), high (catalytic) performance in terms of yield (e.g., about 60-95%) and / or selectivity (about>90%), high catalytic activity, high and / or stable recyclability (e.g., more than about 10 times), high stability in continuous flow systems (e.g., stable drug synthesis in a continuous flow manner), low toxicity, low production / synthesis cost (e.g., about <200 S$ / kg), wide substrate range, and long operating life. In various embodiments, the materials prepared by the embodiments of the methods disclosed herein are easily separated from the product after the reaction, which significantly reduces the operating cost (e.g., about 100 US$ / kg) and ensures the quality of the obtained drug.
[0156] In various embodiments, materials prepared by embodiments of the methods disclosed herein exhibit much greater stability and / or are easily converted to flow processes compared to conventional homogeneous catalytic systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0157] Figure 1A is a diagram showing a method for preparing a material comprising a plurality of geminal metal atom pairs supported on a polymer support (e.g., Cu based on a periodic crystal structure of a host) according to various embodiments disclosed herein. g Schematic diagram of the strategy of using a PCN geminal atom catalyst 100. Figure 1A As shown, the carrier (e.g., polymerized carbon nitride (PCN) 110) comprises H atoms 102, C atoms 104, N atoms 106, and metal (e.g., Cu) ions / atoms 108. One or more NH functional groups 106-102 are present in the carrier as one or more metal coordination sites. When metal (e.g., Cu) single atoms 108a, 108b, 108c, and 108d are introduced, the Cu single atom replaces the H atom 102 via an ion exchange process to coordinate / anchor / load itself on the carrier (wherein the N atom 116) as a pair, thereby obtaining Cu g / PCN112. Figure 1A As shown, Cu gPCN 112 includes multiple geminal Cu pairs coordinated / anchored / supported on a support (eg, see geminal Cu pairs 118a and 118b; and geminal Cu pairs 118d and 118c). The geminal Cu pairs are stabilized by N atoms 116.
[0158] Figure 1B PCN and Cu according to various embodiments disclosed herein are shown g Fourier transform infrared (FTIR) spectrum of / PCN.
[0159] Figure 1C An atomic resolution ADF-STEM image of a geminal Cu structure (see circle) according to various embodiments disclosed herein is shown. The scale bar represents 0.5 nm.
[0160] Figure 1D Cu according to various embodiments disclosed herein is shown g k of PCN and Cu foil as reference 3 Weighted Cu K-edge Fourier transform extended X-ray absorption fine structure (EXAFS) spectrum.
[0161] Figure 1E Cu according to various embodiments disclosed herein is shown g Experimental high-resolution XANES spectra of the calculated XANES data compared with the optimized DFT modeled structure of PCN.
[0162] Figure 2A Cu according to various embodiments disclosed herein is shown g The figure shows the substrate scope of the cross-coupling catalyzed by Cu / PCN on a wide range of biorelevant molecules with (hetero)aryl halides. g =Product yields obtained in the CN bond formation catalyzed by PCN. Reaction conditions (1.4 mol% Cu): CN bond formation, aryl halide (0.2 mmol), nitrogen-based nucleophile (0.24 mmol for N-heterocyclic compounds, 0.3 mmol for primary and secondary amines), 0.4 mmol base (K for N-heterocyclic compounds) 3 PO 4 , NaOH for primary and secondary amines), anhydrous DMSO (1.0 mL), 110° C., 28 h.
[0163] Figure 2B Cu according to various embodiments disclosed herein is shown g The figure shows the substrate scope of the cross-coupling catalyzed by Cu / PCN on a wide range of biorelevant molecules with (hetero)aryl halides. g / Product yields obtained in PCN-catalyzed CO bond formation. Reaction conditions (1.4 mol% Cu): CO bond formation, aryl iodide (0.2 mmol), alcohol (0.4 mmol), KOtBu (0.3 mmol), anhydrous dioxane (2.0 mL), 80°C, 18 h.
[0164] Figure 2C Cu according to various embodiments disclosed herein is shown g The figure shows the substrate scope of the cross-coupling catalyzed by Cu / PCN on a wide range of biorelevant molecules with (hetero)aryl halides. g / PCN-catalyzed CC and CS bond formation. Reaction conditions (1.4 mol% Cu): CC bond formation, aryl halide (0.2 mmol), alkyne (0.3 mmol, for dihalogenated aromatic rings, 0.6 mmol), Cs(OH) 2 .H 2 O (0.3 mmol, 0.6 mmol for dihalogenated aromatic rings) and anhydrous DMSO (1.0 mL), 110°C for 28 h; C-S bond formation, aryl halide (0.2 mmol), thiol / thiophenol (0.3 mmol), NaOtBu (0.30 mmol) and anhydrous dioxane (2.0 mL), 80°C for 18 h.
[0165] Figure 2D Cu according to various embodiments disclosed herein is shown g The figure shows the substrate scope of the cross-coupling catalyzed by Cu / PCN on a wide range of biorelevant molecules with (hetero)aryl halides. g / Product yields obtained in PCN-catalyzed CN, CO, CC, CS bond formation and post-modification.
[0166] Figure 3A The proposed Cu g The catalytic mechanism of CO coupling of / PCN. The figure shows a schematic diagram of the dynamic coordination of the geminal Cu active center.
[0167] Figure 3B The proposed Cu g The catalytic mechanism of CO coupling of / PCN. The figure shows the energy levels of the Cu(II)···Cu(II) interaction, with the proximity increasing from far away (□) to
[0168] Figure 3C The proposed Cu gThe proposed catalytic mechanism of CO coupling of Cu / PCN is shown in the figure. g Reaction mechanism of CO bond formation mediated by / PCN. The spin state, valence state, and Cu···Cu distance are marked in the figure.
[0169] Figure 3D The proposed Cu g The catalytic mechanism of CO coupling of Cu / PCN is shown in the figure. g Calculated energy profile of PCN-mediated CO bond formation.
[0170] Figure 4A The present invention shows that the geminal atom catalyzes Cu according to various embodiments disclosed herein. g Differences in regioselectivity of different copper catalysts over PCN for the synthesis of 1,4-substituted imidazoles.
[0171] Figure 4B It is shown that in the presence of an equivalent amount of terpyridine, Cu g / PCN-catalyzed CN cross-coupling reaction.
[0172] Figure 4C In the synthesis of Dutasteride, the previous route and the Cu according to various embodiments disclosed herein are shown. g Comparison between / PCN pathways.
[0173] Figure 4D Shown is a comparison between the previous Chan-Lam route and the newly designed Ullmann pathway according to various embodiments disclosed herein in the synthesis of xanthine precursors.
[0174] Figure 4E The synthesis of chiral spiro Cp ligand precursors, previous routes and Cu according to various embodiments disclosed herein are shown. g Comparison between / PCN pathways.
[0175] Figure 4F The Cu g Continuous flow synthesis of 1-(4-methylbenzyl)-4-phenyl-1H-1,2,3-triazole as a function of time-on-stream for PCN and Cu tubes. The inset shows the measured concentration of Cu ions leached into solution at the end of each reaction.
[0176] Figure 4GLife cycle assessment (LCA) impact estimates for heterogeneously catalyzed CN coupling (top row) and homogeneously catalyzed CN coupling (bottom row) are shown. Impact contributions are based on Cu according to various embodiments disclosed herein. g / PCN or Cu 2 O+L 1 (L 1 =4,7-dimethoxy-1,10-phenanthroline) in the synthesis of 1-(naphthalen-1-yl)-1H-imidazole by coupling imidazole and 1-iodonaphthalene. For the heterogeneously catalyzed CN coupling, the global warming potential contribution is 38.6% 1-iodonaphthalene; 48.7% imidazole; 7.2% Cu g / PCN; 5.6% DMSO; ecosystem quality contribution is 47.9% 1-iodonaphthalene; 38.7% imidazole; 7.4% Cu g / PCN; 6.0% DMSO; 53.0% 1-iodonaphthalene; 31.8% imidazole; 9.3% Cu g / PCN; 5.9% DMSO; and natural resource contributions of 27.5% 1-iodonaphthalene; 58.9% imidazole; 3.2% Cu g / PCN; 10.4% DMSO. For the homogeneously catalyzed CN coupling, the GWP contribution is 2.9% 1-iodonaphthalene; 3.6% imidazole; 77.1% Cu 2 O / L 1 ; 16.5% N-methyl-2-pyrrolidone; ecosystem quality contribution is 4.1% 1-iodonaphthalene; 3.8% imidazole; 72.7% Cu 2 O / L 1 ; 18.8% N-methyl-2-pyrrolidone; 5.5% 1-iodonaphthalene; 3.3% imidazole; 73.8% Cu 2 O / L 1 ; 17.4% N-methyl-2-pyrrolidone; and natural resource contributions of 2.3% 1-iodonaphthalene; 5.0% imidazole; 75.3% Cu 2 O / L 1 ; 17.4% N-methyl-2-pyrrolidone.
[0177] Figure 5 Cu according to various embodiments disclosed herein is shown gScanning tunneling microscopy (STM) characterization of / PCN. The left figure shows an overview STM image after annealing PCN on Cu(111) at 370K, V=2.0V, I=20pA. The scale bar represents 10nm. The right figure shows the corresponding constant height STM image with a CO functionalized tip (V=5mV, Δz=-20pm; set point before turning off the feedback, V=5mV, I=200pA. The scale bar represents 0.5nm.
[0178] Fig. 6A Cu according to various embodiments disclosed herein is shown g Characterization of PCN. The figure shows a high-resolution TEM image with a corresponding Fourier transform diffraction pattern inset. The scale bar represents 5 nm.
[0179] Figure 6B Cu according to various embodiments disclosed herein is shown g / PCN characterization. The figure shows the ADF-STEM image and the corresponding elemental mapping. The scale bar represents 100 nm.
[0180] Figure 6C Cu according to various embodiments disclosed herein is shown g / PCN characterization. The figure shows the Cu with height distribution inset g AFM images of / PCN.
[0181] Fig.6D Cu according to various embodiments disclosed herein is shown g / PCN characterization. This figure shows PCN and Cu g / PCN XRD pattern.
[0182] Fig. 6E Cu according to various embodiments disclosed herein is shown g / PCN characterization. This figure shows Cu g XPS spectrum of Cu2p of / PCN. The peaks at 932.8eV and 952.7eV are attributed to Cu(I). The solid line and dashed line represent the experimental curve and the fitting curve, respectively.
[0183] Fig. 6F Cu according to various embodiments disclosed herein is shown g / PCN characterization. This figure shows Cu g / PCN and reference CuCl 2 EPR spectrum of .
[0184] Fig. 7A Comparison of experimental and modeled Cu K-edge XANES spectra is shown. The corresponding DFT-modeled atomic structure is shown in the inset.
[0185] Figure 7B Comparison of experimental and modeled Cu K-edge XANES spectra is shown. The corresponding DFT-modeled atomic structure is shown in the inset.
[0186] Figure 7C Comparison of experimental and modeled Cu K-edge XANES spectra is shown. The corresponding DFT-modeled atomic structure is shown in the inset.
[0187] Fig.7D Comparison of experimental and modeled Cu K-edge XANES spectra is shown. The corresponding DFT-modeled atomic structure is shown in the inset.
[0188] Fig. 7E Comparison of experimental and modeled Cu K-edge XANES spectra is shown. The corresponding DFT-modeled atomic structure is shown in the inset.
[0189] Figure 7F Comparison of experimental and modeled Cu K-edge XANES spectra is shown. The corresponding DFT-modeled atomic structure is shown in the inset.
[0190] Figure 7G Comparison of experimental and modeled Cu K-edge XANES spectra is shown. The corresponding DFT-modeled atomic structure is shown in the inset.
[0191] Fig. 8A Cu according to various embodiments disclosed herein is shown g The substrate scope of the cross-coupling and cycloaddition catalyzed by Cu / PCN is shown in the figure. g / The isolated yields of the products obtained in PCN-catalyzed CN bond formation (52-72).
[0192] Figure 8B Cu according to various embodiments disclosed herein is shown g The substrate scope of the cross-coupling and cycloaddition catalyzed by Cu / PCN is shown in the figure. g The isolated yields of the products obtained in the CO bond formation (73-82) catalyzed by PCN are shown. g / Product yields of PCN-catalyzed azide-alkyne cycloadditions (83-90).
[0193] Fig. 9 Cu prepared according to various embodiments disclosed herein is shown g / PCN-catalyzed pharmaceuticals and biorelevant molecules. The figure shows the synthesis of pharmaceutical compounds (91-93) and biorelevant molecules (94-96) from natural products in a multi-step and one-pot manner.
[0194] Fig. 10A Cu with different Cu contents according to various embodiments disclosed herein are shown. 1 / PCN characterization. This figure shows the Cu with different Cu contents 1 ADF-STEM images of the α / β-PCN samples (scale bar: 1 nm). The dotted oval (elliptical shapes) represent GAC sites; the dotted circle (circle / round shapes) represent SAC sites, respectively.
[0195] Fig. 10B Cu with different Cu contents according to various embodiments disclosed herein are shown. 1 / PCN characterization. This figure shows the Cu with different Cu contents 1 FTIR spectrum of / PCN sample.
[0196] Fig. 10C Cu with different Cu contents according to various embodiments disclosed herein are shown. 1 / PCN characterization. This figure shows the Cu with different Cu contents 1 Fourier transform EXAFS spectrum of / PCN sample.
[0197] Fig.11A Cu with different Cu contents according to various embodiments disclosed herein are shown. 1 Electronic structure of / PCN. The figure shows Cu K-edge XANES.
[0198] Fig. 11B Cu with different Cu contents according to various embodiments disclosed herein are shown. 1 The electronic structure of Cu / PCN is shown in the figure. 1 Cu 2p XPS spectrum of / PCN sample.
[0199] Fig. 11C Cu with different Cu contents according to various embodiments disclosed herein are shown. 1 Electronic structure of / PCN 1100. 1102 represents Cu; 1104 represents C; 1106 represents N; and 1108 represents H. The figure shows the charge density distribution and PDOS of a monomeric Cu site.
[0200] Fig.11D Cu with different Cu contents according to various embodiments disclosed herein are shown. 1 Electronic structure of / PCN 1200. The figure shows the charge density distribution and PDOS of the geminal Cu site. 1202 represents Cu; 1204 represents C; 1206 represents N; and 1208 represents H.
[0201] Fig. 12A The Cu according to various embodiments disclosed herein measured before and during the CO coupling reaction are shown. g In situ Cu K-edge XANES and Fourier transform EXAFS spectra of / PCN catalyst.
[0202] Fig. 12B The Cu according to various embodiments disclosed herein measured before and during the CO coupling reaction are shown. g In situ Cu K-edge XANES spectrum of / PCN catalyst.
[0203] Fig. 12C Cu according to various embodiments disclosed herein are shown at different time records in a CO coupling reaction g In situ EPR spectrum of / PCN.
[0204] Fig. 12A , Fig. 12B and Fig. 12C The in situ XANES and EPR spectra during the CO coupling reaction are shown. From the Cu K-edge XANES, it can be clearly seen that Cu g / PCN chemical state changes during the CO cross-coupling reaction cycle. The significant weakening of the characteristic peak at 8983eV and the increase of the main peak at 8996eV indicate that the valence state of Cu increases during the reaction, which is related to the successful adsorption of 4-iodotoluene or methanol. Correspondingly, the intensity of the main peak associated with the first coordination sphere in the Fourier transform EXAFS spectrum increases, proving that the coordination number of Cu increases. The changes in the chemical valence state of Cu during the reaction cycle are further elucidated by the in situ EPR spectrum. EPR-silent Cu(I) is first oxidized to EPR-sensitive Cu(II), where the signal intensity gradually increases, and then reduced to the original Cu(I) state during the completion of the reaction process, which is consistent with the in situ XAFS results.
[0205] Fig.13A Cu according to various embodiments disclosed herein is shown g / PCN in CO coupling. g Cyclic testing of the coupling of 4-iodotoluene with ethanol to form a CO bond using PCN.
[0206] Fig. 13B Cu according to various embodiments disclosed herein is shown g / PCN in CO coupling. This figure shows the stability of the newly prepared Cu g FTIR spectra of / PCN and the catalyst recovered after 9 reaction cycles.
[0207] Fig. 13C Cu according to various embodiments disclosed herein is shown g / PCN in CO coupling. This figure shows the stability of the newly prepared Cu g / PCN and the XRD patterns of the catalyst recovered after 9 reaction cycles.
[0208] Fig.13D Cu according to various embodiments disclosed herein is shown g / PCN in CO coupling. This figure shows the stability of the newly prepared Cu g XPS spectra of / PCN and the catalyst recovered after 9 reaction cycles.
[0209] Fig.13E Cu according to various embodiments disclosed herein is shown g / PCN in CO coupling. This figure shows the stability of the newly prepared Cu g Cu K-edge Fourier transform EXAFS of / PCN and the catalyst recovered after 9 reaction cycles.
[0210] Fig.13F Cu according to various embodiments disclosed herein is shown g / PCN in CO coupling. This figure shows the stability of the newly prepared Cu g XANES spectra of / PCN and the catalyst recovered after 9 reaction cycles.
[0211] Fig.14 The design principles of geminal atom catalysis according to various embodiments disclosed herein are shown, illustrating how the present application overcomes current limitations or previously reported heterogeneous copper catalysts for organic synthesis to provide high specific metal utilization and stability.
[0212] Fig.15A Three independent batches of Cu prepared on a gram scale according to various embodiments disclosed herein are shown. g / PCN photos. Fig.15A , Fig. 15B , Fig. 15C and Fig.15D Experimental procedure for each batch preparation condition shown: CuCl 2 (3.2 g) and PCN (3.5 g) were dispersed in 1000 ml formamide, sonicated for 10 min, then stirred in an oil bath (120 °C) for 12 h, then centrifuged and thoroughly washed several times with ethanol. The oven-dried powder (80 °C) was then heated at 2 °C min -1 The heating rate was 0.15 N / mm2 and the heating rate was 0.15 N / mm2. 2 Keep under the protection of flow for 5 hours.
[0213] Fig. 15B Three independent batches of Cu prepared on a gram scale according to various embodiments disclosed herein are shown. g XRD patterns of / PCN. g scale 1 refers to 18.4 wt% Cu, g scale 2 refers to 18.1 wt% Cu, and g scale 3 refers to 18.6 wt% Cu.
[0214] Fig. 15C Three independent batches of Cu prepared on a gram scale according to various embodiments disclosed herein are shown. g Cu K-edge XANES of MgSO4 / PCN. g scale 1 refers to 18.4 wt% Cu, g scale 2 refers to 18.1 wt% Cu, and g scale 3 refers to 18.6 wt% Cu.
[0215] Fig.15D Three independent batches of Cu prepared on a gram scale according to various embodiments disclosed herein are shown. g Fourier transformed EXAFS spectra of Cu / PCN. g scale 1 refers to 18.4 wt% Cu, g scale 2 refers to 18.1 wt% Cu, and g scale 3 refers to 18.6 wt% Cu.
[0216] Fig.16 Cu according to various embodiments disclosed herein is shown g Reaction curve of CO bond formation catalyzed by / PCN. In a nitrogen-filled glove box, 11 oven-dried screw-top reaction tubes were equipped with magnetic stirring bars. 4-Iodotoluene (0.2mmol×11, 479.7mg), n-butanol (0.4mmol×11, 326.1mg), potassium tert-butoxide (KOtBu, 0.3mmol×11, 370.3mg), decane (0.2mmol×11, 313.0mg) and anhydrous dioxane (2.0mL×11) were added in sequence. The mixture was then shaken to prepare a homogeneous solution. Subsequently, Cu was weighed for each single tube. g / PCN (4.0mg). Afterwards, the above uniform solution was transferred to 11 reaction tubes using a syringe, each with an amount of 2mL. The reaction tubes were sealed with Teflon-lined screw caps, taken out of the glove box, and placed in an oil bath preheated to 80°C for a specified time. After cooling to room temperature, the reaction cap was removed. An aliquot of the solution was transferred to a GC vial and diluted with EtOAc. GC analysis was used to determine the conversion and yield.
[0217] Fig.17 Multi-gram scale Cu is shown according to various embodiments disclosed herein. g / PCN-catalyzed synthesis of p-ethoxytoluene. Experimental procedure for the multi-gram synthesis of p-ethoxytoluene: In a glove box filled with nitrogen, aryl iodide (120 mmol), alcohol (240 mmol), Cu g / PCN (600mg, 1.4mol%Cu), KOtBu (180mmol) and anhydrous dioxane (1200mL) were added to an oven-dried screw-cap reaction bottle equipped with a stirring rod. The reaction bottle was sealed with a Teflon-lined screw cap, taken out of the glove box, placed in an oil bath preheated to 80°C and stirred for 18h. After cooling to room temperature (rt), the lid was removed, and the reaction mixture was concentrated in vacuo with the help of a rotary evaporator. The resulting residue was then purified by silica gel column chromatography to obtain the pure product.
[0218] Fig.18 The preparation of Cu based on the periodic crystal structure of PCN host according to various embodiments disclosed herein is shown. 1 / PCN(SAC) and Cu g / PCN(GAC) strategy.
[0219] Fig.19A Ultra-high density Cu according to various embodiments disclosed herein 1 Characterization of Cu / NC. The figure shows an ADF-STEM image demonstrating the high density of Cu single atoms. The scale bar represents 2 nm.
[0220] Fig.19B Ultra-high density Cu according to various embodiments disclosed herein 1 / NC characterization. This figure shows NC and Cu 1 XRD patterns of / NC. Cu K-edge.
[0221] Fig.19C Ultra-high density Cu according to various embodiments disclosed herein 1 Characterization of Cu / NC. The figure shows CuK-edge XANES (atomic structure shown in the inset).
[0222] Fig.19D Ultra-high density Cu according to various embodiments disclosed herein 1 / NC characterization. 1 Fourier transform EXAFS spectrum of / NC.
[0223] Fig. 20A Cu according to various embodiments disclosed herein is shown g / The geometric structure of PCN 2000. The figure shows the periodic structure optimized by the VASP code. 2002 represents Cu; 2004 represents C; 2006 represents N; and 2008 represents H.
[0224] Fig. 20B Cu according to various embodiments disclosed herein is shown g / The geometric structure of PCN 3000. This figure shows the cluster model used in molecular DFT calculations. 3002 represents Cu; 3004 represents C; 3006 represents N; and 3008 represents H.
[0225] Fig.21A The Cu g Periodic DFT modeling of CH / PCN 3 O and C 6 H 5 Indirect CO coupling to form C 6 H 5 OCH 3 .
[0226] Fig.21B The Cu g Molecular DFT modeling of CH / PCN 3 O and C 6 H 5 Indirect CO coupling to form C 6 H 5 OCH 3 .
[0227] Fig. 21C The Cu g / PCN from CH 3 O and C 6 H 5 Indirect CO coupling to form C 6 H 5 OCH 3 The corresponding schematic structure of the intermediate (c) is shown in FIG. Fig.21A , Fig.21B and Fig. 21C As shown, since the Cu···Cu distance is almost Due to *OCH 3 and *C 6 H 5 Due to the large separation of , direct CO coupling is unlikely. Therefore, an indirect CO coupling pathway was initially considered. In this pathway, B Bonded OCH 3 Will be close to *C 6 H 5 The β-carbon atom near the Cu A (II) Directly bonded *C6 H 5 The indirect route was found to be quite difficult because it involves a spin-forbidden reaction ( 3 IS 4 → 1 IS 5 )and 1 IS 5 → 1 TS 5 The high potential barrier (0.98 eV)
[0228] Fig. 22 The radial distribution probability density (D(r) = r) of Cu(II) atomic orbital (AO) is shown. 2 R(r) 2 ).
[0229] Fig.23 Shown is the calculated energy distribution of C-O bond formation catalyzed by isolated single atoms.
[0230] Fig.24 It is shown that without the help of base, C 6 H 5 I and CH 3 OH is directly dehalogenated and dehydrogenated to form *C 6 H 5 +CH 3 The energy distribution of the reaction of O*+HI. Calculation shows that C 6 H 5 I and CH 3 The co-adsorption of OH on two Cu(I) atoms has an adsorption energy of -1.27 eV (singlet 1 IS 0 → Singlet 1 IS). However, C 6 H 5 Direct dehalogenation of I and CH 3 Dehydrogenation of OH to form HI and *C adsorbed on the Cu(II) sites on the surface 6 H 5 and CH 3 The O* species is strongly endothermic (2.52 eV), which means it will have a much higher reaction barrier. Note that by C 6 H 5 and CH 3 Direct bonding of O and copper, Cu(I,d 10 )···Cu(I,d 10 ) sites are converted to oxidized Cu(II, d 9 )···Cu(II,d 9 ) site. Therefore, from the singlet state1 IS to triplet 3 FS 0 The direct dehalogenation and dehydrogenation reactions are spin-forbidden reactions, and no attempt was made to determine their reaction barriers. This result is consistent with the experimental fact that the reaction cannot occur without the addition of a strong base.
[0231] Fig.25 Direct dehydrogenation of CH by KOtBu is shown 3 OH and then C 6 H 5 I dehalogenation to Cu g / PCN forms Cu(II)*C 6 H 5 +CH 3 O*Cu(II) reaction energy profile, where KI and HOtBu are released in solution. When a strong base like KOtBu is added to the system, it will immediately cause CH 3 OH deprotonates to form K + -OCH 3 and HOtBu(singlet 1 IS 1 → Singlet 1 IS 2 ), where the exothermicity is -2.41 eV. This process is quite easy because the CH 3 Compared with OH (15.5), HOtBu (17.0) has a higher pKa. + -OCH 3 and weakly adsorbed C 6 H 5 I to form KI salt and *C adsorbed on the Cu(II) sites on the surface 6 H 5 and CH 3 The O* species will again be difficult as it involves another spin-forbidden reaction to form C 6 H 5 -Cu(II,d 9 ) and Cu(II,d 9 )-OCH 3 Although this process (singlet 1 IS 2 →Triplet 3 IS 3 ) is only slightly endothermic (-0.33 eV), but the reaction rate of this spin-forbidden reaction will be very low because a singlet-to-triplet spin crossover is required via relatively small spin-orbit coupling, making this process the rate-determining step (RDS) of the entire reaction. In fact, experimentally, EPR measurements determined the formation of Cu(II) during the reaction. In addition, the key role of the KOtBu strong base and the experimentally observed C6 H 5 I <C 6 H 5 Br< <C 6 H 5 The reaction time of Cl is consistent with the calculated result. It is worth mentioning that during nucleation, KI molecules will form KI solid deposits to drive the chemical equilibrium toward the triplet state. 3 IS 3 Product formation.
[0232] Fig.26 The Cu measured under CO coupling reaction conditions is shown in g EPR spectrum of / PCN.
[0233] Fig. 27 Cu 2+ is bonded to an aryl halide (4-iodobenzene) and an alcohol (methanol). g Calculated PDOS of Cu sites in / PCN. In brief, before and after reactant adsorption ( Fig. 27 )Cu g Comparison of the PDOS in / PCN shows that the interaction with the reactants shifts the PDOS of the copper center to higher energies, crossing the Fermi energy (E F ). This is because the copper atoms lose more electrons to the adsorbed reactants, as supported by the Bader charge analysis (Table 4). In addition, adsorption changes the non-spin polarized electronic state of copper to an average magnetic momentum of 1μ B / Spin-polarized electronic states of Cu.
[0234] Fig.28A The Cu containing 18.3 wt.% (GAC) or 1.8 wt.% (SAC) Cu is shown. 1 / PCN-catalyzed kinetic study of CO bond formation. The natural logarithm of the concentration of aryl halide versus time: The initial concentration of aryl halide C 0 =0.05M (upper left), C 0 = 0.1 M (top right and bottom). All reactions were performed with 1.4 mol % Cu. Fig.28A , Fig.28B and Fig.28C Experimental procedure: In N 2 In a glove box filled with 1.4 mol.% Cu 1 / PCN (for 18.3wt.%Cu 1 / PCN corresponds to 1.0 mg or for 1.8 wt.% Cu 1 / PCN corresponding to 10 mg) was added to each of 5 oven-dried screw-top reaction tubes equipped with a stir bar. Subsequently, 0.1 mmol (C 0 =0.05M) or 0.2mmol(C 0 =0.1M) of 4-iodotoluene, 0.4mmol n-butanol, 0.3mmol KOtBu and 0.2mmol decane (internal standard for GC analysis) were added to each reaction tube. The reaction tube was sealed with a Teflon-lined screw cap, removed from the glove box, and placed in an oil bath preheated to 80°C for the required time (1-5h). After cooling to room temperature, the reaction cap was removed. An aliquot of the solution was transferred to a vial, diluted with EtOAc, and the reactant conversion was analyzed by gas chromatography. Under the optimized reaction conditions, the natural logarithm of the concentration of the aryl halide was linear with respect to time, indicating that the reaction was a first-order reaction in the aryl halide. Consistently, with Cu having a metal content of 18.3wt.%, the reaction was carried out under the same conditions as in the reaction mixture. g Compared with the PCN catalyst, the first-order rate constant (-slop, h) at an initial concentration of 0.05 M or 0.1 M based on 1.4 mol% Cu was -1 ) are very similar (0.431h -1 or 0.448h -1 ). Therefore, the aryl halide may be involved in the rate-limiting step. This finding is consistent with computational studies that predict the activation of 4-iodobenzene (from IS2 to IS3, see Figure 3C ) is rate limiting. In contrast, using 1.8wt.%Cu 1 The reaction of the / PCN catalyst was significantly slower than that of the 18.3wt.%Cu g / PCN catalyst, despite the introduction of an equivalent amount of copper (1.4 mol%) into the reaction. In contrast, the first order rate constant is 5.5 times higher than that of the material containing 18.3 wt.% copper, which is consistent with the higher yield observed with this catalyst.
[0235] Fig.28B The Cu containing 18.3 wt.% (GAC) or 1.8 wt.% (SAC) Cu is shown. 1 / PCN-catalyzed kinetic study of CO bond formation. The natural logarithm of the concentration of aryl halide versus time: The initial concentration of aryl halide C 0 =0.05M (upper left), C 0 = 0.1 M (top right and bottom). All reactions were performed with 1.4 mol % Cu.
[0236] Fig.28CThe Cu containing 18.3 wt.% (GAC) or 1.8 wt.% (SAC) Cu is shown. 1 / PCN-catalyzed kinetic study of CO bond formation. The natural logarithm of the concentration of aryl halide versus time: The initial concentration of aryl halide C 0 =0.05M (upper left), C 0 = 0.1 M (top right and bottom). All reactions were performed with 1.4 mol % Cu.
[0237] Fig.29A NMR shows that Cu g Analysis of products from Ullmann-type coupling of 1H-Pd / PCN.
[0238] Fig.29B NMR shows that Cu g Analysis of products from Ullmann-type coupling of 1H-Pd / PCN.
[0239] Fig.29C NMR shows that Cu g Analysis of products from Ullmann-type coupling of 1,2-dihydro- ...
[0240] Fig.30 The Cu used in the CO coupling reaction is shown. g ADF-STEM image of the MgO / PCN catalyst. The scale bar indicates 2 nm.
[0241] Fig.31A Shown by Cu g Cyclic test of the coupling of 4-iodotoluene with ethanol to form a CO bond using PCN.
[0242] Fig.31B Shown by Cu g / PCN to couple 4-iodotoluene with ethanol to form a CO bond. g / PCN and XRD patterns of the catalyst after 4 reaction cycles. For the first four cycles, the catalyst was washed with dioxane before being used in the next cycle reaction. For reactivation, the catalyst was carefully washed with ethanol and water to remove KI before being used in the fifth reaction cycle.
[0243] Fig.31C Shown by Cu g / PCN to couple 4-iodotoluene with ethanol to form a CO bond. gCu K-edge XANES of the catalyst after 4 reaction cycles. For the first four cycles, the catalyst was washed with dioxane before being used in the next cycle reaction. For reactivation, the catalyst was carefully washed with ethanol and water to remove KI before being used in the fifth reaction cycle.
[0244] Fig.31D Shown by Cu g / PCN to couple 4-iodotoluene with ethanol to form a CO bond. g Fourier transform EXAFS spectra of the catalyst after 4 cycles of reaction. For the first four cycles, the catalyst was washed with dioxane before being used in the next cycle reaction. For reactivation, the catalyst was carefully washed with ethanol and water to remove KI before being used in the fifth reaction cycle. Fig.31A , Fig.31B , Fig.31C and Fig.31D As shown, the deposited insoluble KI salt can be clearly seen from the XRD pattern, where a complete set of peaks attributed to KI crystals appears in the used catalyst. Meanwhile, the Cu K-edge Fourier transform EXAFS and XANES spectra show that the coordination and electronic structure of the copper atoms before and after the reaction are the same, which means that the deposited KI salt only physically covers the surface of the catalyst, rather than chemically binding to the copper sites.
[0245] Fig.32A shows a continuous flow setup for evaluating catalytic performance. g / PCN-catalyzed CO bond formation.
[0246] Fig.32B shows a continuous flow setup for evaluating catalytic performance. g / PCN-catalyzed azide-alkyne cycloaddition.
[0247] Fig.32C Shown is a continuous flow setup for evaluating catalytic performance. The figure shows azide-alkyne cycloaddition catalyzed by a Cu tube.
[0248] Fig.33 The flow rate of Cu g Continuous Flow Synthesis of Ethoxybenzene from PCN.
[0249] Fig.34A Sankey diagram showing the GWP flow for homogeneous and heterogeneous catalyzed CN coupling. The contribution is based on Cu g / PCN( Figure 2A) in the synthesis of product 1, as defined by IPCC 2021, in kg CO per kg product 2 The analysis takes into account the optimized conditions reported for both systems. For simplicity, only the contribution above the 3% cutoff is shown.
[0250] Fig.34B Sankey diagram showing the GWP flow for homogeneous and heterogeneous catalyzed CN coupling. The contribution is based on Cu 2 O+L 1 (Table 2, entry 2) Performance in the synthesis of product 1, as defined by IPCC 2021, in kg CO per kg product 2 The analysis takes into account the optimized conditions reported for both systems. For simplicity, only the contribution above the 3% cutoff is shown.
[0251] Fig.35 Shown are the comparative impacts derived from an ex ante LCA of using a homogeneous or heterogeneous catalyst in one of the studied CN coupling reactions based on four sustainability metrics: midpoint global warming potential, ecosystem quality, endpoint human health and resources. The base case considers a single use of the catalytic system. Reported values are 1 per 1 kg of product. DALY = daily adjusted life year.
[0252] Fig.36A Shown is a sensitivity analysis of the solvent (a) recyclability of the reaction mixture for homogeneous and heterogeneous catalytic systems in CN coupling reactions.
[0253] Fig.36B A sensitivity analysis of the catalyst recyclability of the reaction mixture of a homogeneous and heterogeneous catalytic system in a CN coupling reaction is shown. Fig.36A and Fig.36B As shown in g / PCN or Cu 2 O / L 1) and the solvent can be reused multiple times by recovering them from the reaction medium without any energy loss, repeating the LCA calculations assuming a 1% loss of catalyst and solvent in each cycle and neglecting potential catalyst deactivation. The sensitivity analysis thus complements the evaluation of the two catalytic systems presented in the main manuscript, covering the performance of a wide range of more efficient homogeneous and heterogeneous systems with different catalyst and solvent requirements. In the heterogeneous case, recycling does not significantly affect the overall impact, as this is mainly given by the reactants. In contrast, the carbon footprint of the homogeneous system decreases with the level of recyclability, first sharply and then with a gentle slope as the bottleneck starts to shift to the reactants. After reusing the catalyst and solvent 100 times under these ideal conditions, the heterogeneous system will still outperform the homogeneous system. The results therefore indicate that it is very unlikely to find a homogeneous system that significantly outperforms its heterogeneous counterpart.
[0254] Example
[0255] From the following examples, tables and, if applicable, in conjunction with the accompanying drawings, the example embodiments of the present disclosure will be better understood and apparent to those of ordinary skill in the art. It should be understood that other modifications associated with structural and / or chemical changes may be made without departing from the scope of the present invention. The example embodiments are not necessarily mutually exclusive, as some example embodiments may be combined with more than one embodiment to form new example embodiments. The example embodiments should not be construed as limiting the scope of the present disclosure.
[0256] The following examples describe a new class of heterogeneous geminal atom catalysts (GACs) that pair single-atom sites with specific coordination and spatial proximity. Regularly separated nitrogen-related anchor groups with delocalized π-bond properties in a polymeric carbon nitride host allow the synthesis of ground-state separations at high metal density. Cu geminal site. The adaptive coordination of a single Cu site in GAC enables a synergistic bridge coupling pathway via dynamic Cu-Cu bonding for cross-coupling of different CX (X=C, N, O, S) with low activation barriers. In the following examples, in situ characterization and quantum theoretical studies show that this dynamic process is triggered by adsorption of only two different reactants through the geminal metal site, making homo-coupling infeasible. These intrinsic advantages of GAC enable the efficient assembly of challenging heterocycles with multiple coordination sites, sterically crowded scaffolds, and drugs with highly specific and stable activity. Scale-up experiments and conversion to continuous flow demonstrate its broad applicability in fine chemical manufacturing.
[0257] Example 1: Heterogeneous Geminal Atom Catalyst (GAC)
[0258] A new class of heterogeneous geminal atom catalysts (GACs) composed of regularly separated pairs of low-valence single-atom metal sites has been developed that provides a powerful, economically important, and versatile platform to address long-standing reactivity challenges beyond traditional cross-coupling protocols, enabling us to achieve environmentally benign organic syntheses by tuning the properties and combinations of geminal metals to promote industrially critical coupling reactions.
[0259] A newly developed class of heterogeneous geminal atom catalysts (GACs) contains pairs of low-valence metal centers with regular ground-state separation and suitable coordination dynamics to achieve site synergy. In the following examples, the concept of copper atoms anchored on nanocrystalline polymeric carbon nitride supports is demonstrated, which defines ~ The proximity of metal sites to the catalyst and enables their adaptive coordination during reactions. Catalytic evaluation in a wide range of cross-coupling reactions, including azide-alkyne cycloadditions, carbon-carbon, and carbon-heteroatom bond formations, demonstrates the superior performance of GAC compared to conventional SACs with similar metal density based on nitrogen-doped carbon hosts. The results show that GAC overcomes the long-standing problem of slow oxidative addition in copper-catalyzed cross-coupling reactions, which has limited the scope of copper compared to palladium, despite its lower cost and carbon footprint. Detailed structural and mechanistic analysis confirms the synergistic role of the metal center in the geminal site, enabling efficient activation of substrates through an unprecedented dynamic bridge coupling mechanism. Further demonstration of biorelevant drug production and conversion to continuous flow illustrates the broad synthetic capabilities of GAC compared to established heterogeneous catalysts. The environmental benefits of the GAC pathway here compared to traditional homogeneous synthesis are quantified via an ex ante life cycle assessment (LCA), highlighting the substantial reduction in footprint across four recognized metrics.
[0260] Example 2: Synthesis and characterization of geminal catalysts
[0261] A stepwise ion exchange and ligand removal strategy was designed to exploit the abundant and periodic presence of NH functional groups as metal coordination sites in polymeric carbon nitrides to synthesize low-coordinated geminal metal atoms (PCN, Figure 1A and Fig.15A , Fig. 15B , Fig. 15C and Fig.15D ). When introduced, Cu single atoms replace H atoms, as evidenced by the almost complete reduction in the intensity of the vibrational bands associated with the NH group of PCN ( Figure 1B ), and is further stabilized by the relative N atoms. g / PCN (18.3wt.%Cu) obtained by annular dark field scanning transmission electron microscopy (ADF-STEM, Figure 1C) revealed a high concentration of metal atoms that tend to form regularly spaced pairs (called geminal Cu) with an average Cu-Cu distance of ~0.4 nm. Such geminal Cu pairs anchored in PCN chains were also captured by in situ scanning tunneling microscopy characterization ( Figure 5 Elemental mapping using energy dispersive X-ray spectroscopy (EDS) and powder X-ray diffraction (XRD) measurements also confirmed the presence of Cu g Homogeneous metal dispersion in PCN and absence of nanoparticles or clusters ( Fig. 6A , Figure 6B , Figure 6C , Fig.6D , Fig. 6E and Fig. 6F ). Consistently, the Fourier transform extended X-ray absorption fine structure (EXAFS, Figure 1D and Table 1) The spectra reveal The main features of the center and the The weak peaks at 1s→4p correspond to the interatomic distances of the first shell Cu-N and the second shell Cu-C, respectively. The prominent pre-edge feature at about 8983 eV in the Cu K-edge X-ray absorption near-edge structure (XANES) can be attributed to the 1s→4p xy transition, indicating diagonally coordinated Cu. To confirm the atomic structure of the Cu site, first-principles calculations based on density functional theory (DFT) were performed to identify possible models and simulate their corresponding XANES spectra. Fig. 7A , Figure 7B , Figure 7C , Fig.7D , Fig. 7E , Figure 7F and Figure 7G ), the structure consisting of heptazine chains shows the best agreement with the experimental Cu K-edge XANES spectrum ( Figure 1E This diagonally coordinated N-Cu-N structure confers a +1 Cu valence state, and the monovalent Cu(I) state is further confirmed by X-ray photoelectron spectroscopy and electron paramagnetic resonance spectroscopy (EPR, Fig. 7A , Figure 7B , Figure 7C , Fig.7D , Fig. 7E , Figure 7F and Figure 7G ).
[0262] Table 1 |Cu g / PCN and Cu 1 EXAFS fitting results of / NC.
[0263]
[0264] N, coordination number; R, distance between absorbing and backscattering atoms; σ 2 , Debye-Waller factor, used to account for thermal and structural disorder; R factor as a measure of goodness of fit. Cu g / PCN and Cu 1 The fitted coordination environment of / NC agrees well with the structure proposed from DFT.
[0265] Example 3: Performance in cross-coupling reactions
[0266] In order to evaluate Cu g The reactivity range of the / PCN catalysts was investigated under ligand-free conditions with various (hetero)aryl halides with different electronic and / or steric properties (Table 2 and Fig.16 ). The results show that Cu g / PCN is an efficient heterogeneous catalyst for general cross-coupling reactions, converting different reactants into target molecules with high selectivity and yield. Figure 2A , Figure 2B , Figure 2C and Figure 2D as well as Fig. 8A and Figure 8B ). Aryl and heteroaryl iodides and bromides are excellent coupling partners, providing a broad spectrum of products (1-82) in good to excellent yields. Electron donating, electron withdrawing, functional substituents (e.g., hydroxyl, amino, halide, ester, ketone, nitrile, alkene, alkyne), and heterocycles are well tolerated, providing great flexibility for further synthetic manipulation. In particular, nitrogen heterocycles (1-11, 52-61), amides (12-14, 62), sulfonamides (15), arylamines (16, 17, 63-69), and alkylamines (18-21, 70) all participate in CN couplings to produce different functionalized nitrogen-containing compounds. Fluorinated alcohols (33, 82) and deuterated methanols (32, 80, 81) are effective substrates for CO couplings. Synthetically useful CC couplings can also be achieved using terminal alkynes (38-42) or electron-poor (hetero)arenes (43, 44). At the same molar equivalent of copper, the GAC system outperformed the copper nanocatalyst and the benchmark homogeneous cuprous iodide (Table 3). g / PCN also showed excellent performance for azide-alkyne cycloadditions (83-90, 88-94% yield), which is known to involve two metal centers, such as described in Worrell, B., Malik, J., and Fokin, VV. Direct evidence of a dinuclear copper intermediate in Cu(I)-catalyzed azide-alkyne cycloadditions. Science 340, 457-460 (2013), the contents of which are fully incorporated herein by reference. Cu g The PCN-catalyzed cross-coupling is scalable: the production of p-ethoxytoluene (22) was successfully carried out on a 26 g scale, affording the CO coupling product ( Fig.17 ).
[0267] The compatibility of the GAC system was further tested on biologically relevant molecules. Representative examples of cross-coupling involved DL-menthol (94, 95), stigmasterol (50), DL-isoborneol (96), 1,2,3,4-diacetonegalactose (48), and derivatives of testosterone (49) and prednisolone (51). Figure 2A , Figure 2B , Figure 2C and Figure 2D as well as Fig. 9 ) and the large-scale synthesis of drug-like p-arylthioaniline (47, 1.2 g) proceeded smoothly to provide the corresponding products, highlighting the Cu g The applicability of PCN catalysts for late-stage modification of complex molecules was also demonstrated. Starting from commercially available substrates, the bulk synthesis of selected pharmaceutically active compounds (91-93) was also successfully accomplished ( Fig. 9 ).
[0268] Table 2 | Optimization of CO coupling reaction conditions. 2 Conditions: 4-iodotoluene (1.0 equivalent), ethanol (2.0 equivalent), Cu g / PCN catalyst (1 mg), base (1.5 eq), solvent (2 mL), 80°C, 18 h, 0.2 mmol scale.
[0269]
[0270]
[0271] Table 3 | Comparison of turnover numbers (TON) reported for copper catalysts in the Ullmann reaction.
[0272]
[0273]
[0274]
[0275] a Entries 1-10 estimated from reported product yields
[0276] b L 1 =4,7-dimethoxy-1,10-phenanthroline; L 2 =β-ketoester; L 3 =8-hydroxyquinalidine; L 4 =(1E,2E)-oxalaldehyde dioxime; L 5 = all-6-amino-β-cyclodextrin; TON = [moles of converted aryl halide / [moles of Cu catalyst] × 100%;
[0277] CE: Comparative example.
[0278] Example 4: Reaction Mechanism
[0279] To confirm the unique site synergy in GAC, a series of Cu single-atom catalysts (Cu) with Cu contents ranging from 0.2 to 18.3 wt.% were prepared. 1 / PCN), where the ratio of monomeric Cu(I) to geminal Cu(I)···Cu(I) sites is expected to decrease with increasing Cu content in the sample ( Fig.18 ). Meanwhile, detailed characterization ( Fig. 10A , Fig. 10B and Fig. 10C ) and quantum theory studies based on DFT calculations ( Fig.11A , Fig. 11B , Fig. 11C and Fig.11D ) revealed the same chemical state of each Cu regardless of the metal content. The same amount of Cu (2 mol%) was used to evaluate Cu with different Cu contents. 1 / PCN catalysts for CN, CO cross-coupling and azide-alkyne cycloaddition catalytic performance (Table 4). Similar trends were observed in all cases: product yields were correlated with metal content, increasing from zero in samples containing 0.2 wt.% Cu. Among them, all Cu(I) sites were isolated monomers, with about 90% by the catalyst with the highest content of geminal sites. This control experiment revealed that monomeric Cu(I) was incapable of triggering the coupling reaction because of the high energy barrier for the oxidation of low-valent copper to trivalent Cu(III) intermediates, highlighting the necessity of geminal Cu(I)···Cu(I) structure. In addition, the low valence state of the metal center imparted by the diagonally coordinated N-Cu-N structure also plays an important role in the activation of the reactants. This is in sharp contrast to the zero activity observed for CO coupling reactions on ultra-high density divalent single-atom Cu(II) on nitrogen-doped carbon, even if the catalyst contains a large number of adjacent CuN 4 Site( Fig.19A , Fig.19B , Fig.19C and Fig.19D ).
[0280] Given the well-documented difficulties of oxidative addition on Cu, this study performed quantum theoretical studies (periodic and cluster models, Fig. 20A and Fig. 20B ) to explore the coupling of 4-iodobenzene with methanol to obtain Cu g A molecular-level understanding of the formation of PCN-mediated cross-links is presented. Initiation is induced by the (hetero)aryl halide (4-iodobenzene) and the partner nucleophile (methanol) via individual adsorption of each Cu(I) atom at the geminal site. Comprehensive theoretical calculations of plausible mechanisms strongly support the preference for a direct coupling pathway, where the dynamically formed Cu with direct Cu-Cu bonding 2 The dimer promotes C-O bond formation via oxidative addition and subsequent elimination to produce C 6 H 5 OCH 3 ( Fig.21A , Fig.21B and Fig. 21C The unique heptazine chain structure allows geminal Cu (named Cu A and Cu B ) migrate adaptively toward each other when adsorbing reactants ( Figure 3A and Table 5), so that the two reactants (*C 6 H 5 and *OCH 3 ) are close enough for direct cross-link bond formation. After product desorption, the system naturally returns to the original static state with unbonded Cu(I)···Cu(I) sites ( Figure 3C and Figure 3D). This dynamic reconfiguration of geminal Cu sites during the reaction is expected to be energetically expensive, which can be largely offset by the electronic energy gain of Cu-Cu bonding orbital interactions. Due to the quantum primogenic effect, the atomic radial orbits of Cu 4s in the radial probability distribution are extended by Much larger than Cu 3d ( Fig. 22 ), so Cu 2 The formation of the dimer is energetically compensated via Cu-Cu 4s-4s bonding. In fact, chemical bonding analysis shows that when direct 4s-4s bonds are formed, the 4s-4s orbital interactions between geminal Cu(II) will cause the system to undergo a transition from Cu to II (d 9 s 0 )···Cu II (d 9 s 0 ) triplet to Cu II (d 8 s 1 )-Cu II (d 8 s 1 )The potential energy surface of the singlet state crosses ( Figure 3B ). Furthermore, DFT calculations indicate that an alternative pathway involving simultaneous oxidative addition of both reactants via a single copper has a much higher barrier (>2.45 eV), thus ruling out the possibility of a cross-coupling reaction via isolated single copper atoms ( Fig.23 ).
[0281] In addition, our theoretical calculations revealed that the adsorption states of individual Cu sites in GAC exhibit negligible mutual influence, which is different from traditional static diatomic or bimetallic complex catalysts with strong direct or indirect metal-metal interactions. More importantly, the co-adsorption process can only occur in the combination of 4-iodobenzene and methanol (neither two 4-iodobenzene nor two methanol molecules), which can explain why only cross-coupling products are obtained in the CO coupling reaction instead of homo-coupling products ( Fig.24 and Fig.25 ). The adsorption of 4-iodobenzene and methanol on the Cu sites resulted in a critical Cu(I) to Cu(II) valence state conversion, which was directly demonstrated by EPR spectroscopy measurements ( Fig.26 ), where Cu g EPR-silent Cu(I, d 10 s 0 ) is oxidized to EPR-sensitive Cu(II, d 9 s 0 ). For the calculated PDOS( Fig. 27 ) and Cu g The change of Bader charge of Cu in / PCN (Table 6) and further analysis of spin density population confirmed that Cu 6 H 5 or *CH 3 The valence state of O after that changes to Cu(II), which is consistent with the EPR results. In addition, the calculated energy distribution reveals the activation of 4-iodobenzene with an activation barrier greater than 0.98 eV, representing the rate-determining step of CO coupling, which is consistent with the experimental results ( Fig.28A , Fig.28B and Fig.28C ). Through in situ XAFS and EPR experiments ( Fig. 12A , Fig. 12B and Fig. 12C ) further validate the proposed theoretical framework, which effectively tracks the chemical states and local bonding environment evolution of Cu species during the entire reaction cycle.
[0282] Table 4 | Cu with different copper contents 1 Catalytic performance of / PCN in different reactions.
[0283]
[0284] a 1-Chloro-4-iodobenzene (0.2 mmol), imidazole (0.24 mmol), Cu 1 / PCN(2mol%Cu),K 3 PO 4 (0.4 mmol), decane (0.2 mmol), anhydrous DMSO (2.0 mL), 110 °C, 28 h.
[0285] b 4-Iodotoluene (0.2mmol), ethanol (0.4mmol), Cu 1 / PCN (2 mol% Cu), KOtBu (0.3 mmol), decane (0.2 mmol), anhydrous dioxane (2.0 mL), 80°C, 18 h.
[0286] c Ethynylbenzene (0.2 mmol), 1-(azidomethyl)-4-methylbenzene (0.6 mmol), Cu 1 / PCN (2 mol% Cu), decane (0.2 mmol), 1:1 water / acetonitrile (3.0 mL), 60°C, 24 h.
[0287] The yield was determined by gas chromatography.
[0288] Table 5 | Atom numbering of the active site and calculated bond distances and Wiberg bond orders of IS5 and IS6 intermediates.
[0289]
[0290]
[0291] Table 6 | Cu at various stages of CO coupling reaction g / The charge density of Cu atoms in PCN (ΔQ, in e - ) analysis. The definitions of initial state (IS), transition state (TS) and final state (FS) are similar to Fig.21A Same as presented in .
[0292]
[0293] Example 5: Unique advantages of geminal atom catalysis
[0294] The Cu g / PCN's versatility( Figure 4A , Figure 4B , Figure 4C , Figure 4D and Figure 4E Compared with the benchmark homogeneous 1,10-phenanthroline-linked copper catalyst, Cu g / PCN exhibited enhanced regioselectivity, demonstrating the major advantage of GAC in promoting the formation of multifunctional heterocycles commonly found in natural products and pharmaceuticals ( Figure 4A , Fig. 8A and Figure 8B as well as Fig.29A , Fig.29B and Fig.29C ). Hopefully, Cu g / PCN's performance in CN coupling reactions is not impaired by exogenous equivalents of terpyridine ( Figure 4B ), highlighting the catalyst's tolerance to multi-coordinate entities. g The PCN / PCN catalyst addresses practical shortcomings of reported synthetic routes to the synthesis of challenging drugs. For example, a more readily available bromide substrate (this work, 1.4 mol% Cu catalyst, 62% yield) was successfully used for CN coupling (previous iodide substrate, 3 equivalents Cu powder, 53% yield), improving the overall synthesis of dutasteride (98), a synthetic 4-azasteroid derivative used primarily for the treatment of prostate diseases ( Figure 4CSimilarly, a more efficient and cost-effective Ullmann coupling using bromide substrates (present work, 1.4 mol% Cu catalyst, 65% yield) was designed as an alternative to the previously reported Chan-Lam coupling involving more expensive boronic acids (2 equiv. Cu complex, 38% yield) for the synthesis of precursors of xanthine derivatives useful as kinase inhibitors (99) ( Figure 4D ). By using a catalytic amount of recyclable Cu g / PCN, stoichiometric amounts of copper waste can be avoided, which would otherwise lead to product contamination and other environmental problems. g / PCN demonstrated its ability to promote cross-coupling reactions involving sterically demanding substrates, enabling the synthesis of precursors to chiral spiro Cp ligands (100), which are important in asymmetric catalysis. g This direct cross-coupling of 1H / PCN afforded the precursor in a single step with a 52% yield, compared to a previous route that required three steps to deliver 100 in 22% overall yield, as the previous route was inefficient in direct cross-coupling with isopropanol in the presence of a homogeneous copper-based catalyst ( Figure 4E ). These examples emphasize that Cu g The ability of PCNs to overcome challenges in organic synthesis makes them attractive candidates for practical adoption in the production of fine chemicals.
[0295] Another key advantage of using heterogeneous catalysts is their recyclability and reusability. Fig.13A , Fig. 13B , Fig. 13C , Fig.13D , Fig.13E and Fig.13F As shown, Cu g / PCN exhibited excellent durability and recyclability in CO coupling reactions, with no appreciable decrease in conversion and selectivity over nine consecutive runs. Consistently, ICP-AES analysis of the spent catalyst confirmed that the amount of Cu was comparable to that of fresh Cu g / PCN is almost the same, and there is no detectable Cu ion in the solution. g The ADF-STEM images obtained for the Cu / PCN catalysts show a high density of atoms with no visible nanoparticle agglomeration, indicating that the atomic dispersion of the Cu species is preserved after the catalytic reaction ( Fig.30 FTIR, XRD, XPS, Cu K-edge XANES, and EXAFS analyses also revealed that the atomic structure of Cu in the spent catalyst is similar to that of fresh Cu g / PCN same( Fig.13A , Fig. 13B , Fig. 13C , Fig.13D , Fig.13E and Fig.13F In addition, the coupling of 4-iodotoluene with ethanol was carried out under 0.01 mol% Cu (Cu g / PCN) to afford the desired product in 80% yield, corresponding to a turnover number (TON) of 8000, which is almost two orders of magnitude higher than the homogeneous copper-catalyzed cross-coupling of aryl halides with aliphatic alcohols. It is worth noting that the obtained TON value may be underestimated due to the blocking of active sites by the deposition of insoluble salts ( Fig.31A , Fig.31B , Fig.31C and Fig.31D ). In addition, motivated by major developments in improving synthesis efficiency and chemical process intensification, the research will be conducted through Cu g The batch synthesis of PCN was converted into a continuous flow scheme, which has obvious advantages in automation and process optimization ( Fig.32A , Fig.32B and Fig.32C Evaluation in a custom packed bed reactor demonstrated stable gradient production of ethoxybenzene at different flow rates ( Fig.33 ) and 1-(4-methylbenzyl)-4-phenyl-1H-1,2,3-triazole were produced constantly in flow for more than 144 h with no significant change in selectivity or yield ( Figure 4F ), and negligible leaching of Cu ions into solution compared to commercially available copper tube flow reactors ( Figure 4F ).
[0296] Finally, this study quantifies the environmental benefits of geminal atom catalysis routes compared to traditional homogeneous synthesis by LCA. This analysis provides a detailed cradle-to-gate evaluation of the impact of all reaction components, reveals a substantial reduction in the environmental footprint of heterogeneous catalysts, and highlights the major contribution of ligands in homogeneous systems. Figure 4G and Fig.34A , Fig.34B and Fig.35 ). In addition, sensitivity analysis of the LCA results showed that it would be difficult to find homogeneous counterparts that exhibit significantly better environmental performance, since the contribution of catalysts and solvents to the total impact in heterogeneous systems is already low ( Fig.36A and Fig.36B ).
[0297] Example 6: Summary
[0298] In summary, the design of geminal metal single-atom catalysts anchored on polymeric carbon nitride has been demonstrated above, demonstrating their promising potential in heterogeneously catalyzed cross-coupling reactions. The specific proximity of two paired, low-valent, and electronically separated geminal metal centers allows for a synergistic bridging cross-coupling mechanism, resulting in greatly enhanced efficiency compared to conventional monomeric metal sites in single-atom catalysts. This catalytic platform enables the concise and cost-effective construction of complex pharmaceutical compounds, outperforming state-of-the-art homogeneous catalytic systems in terms of applicability and synthetic scope. In addition to addressing the long-standing oxidative addition challenges of copper-based catalysts, the concept of geminal atom catalysis with dynamic active sites provides a generalizable framework to obtain a myriad of catalysts to suit different synthetic needs by tuning the types and combinations of geminal metal centers.
[0299] Example 7: Method
[0300] 7.1. Synthesis of Polymeric Carbon Nitride (PCN)
[0301] The crucible was heated at 550 °C (heating rate of 2.3 °C min -1 ) was calcined in static air for 3 h to prepare bulk PCN. -1 ) was thermally stripped in static air for 5 h to obtain the stripped PCN. The stripping process can be cycled several times until the PCN is effectively stripped.
[0302] 7.2. Cu g Synthesis of PCN
[0303] CuCl 2 (0.64 g) and exfoliated PCN (0.70 g) were dispersed in 200 ml formamide, sonicated for 10 min, then stirred in an oil bath (120 °C) for 12 h, then centrifuged and thoroughly washed several times with ethanol. The oven-dried powder (80 °C) was then heated at 2 °C min -1 The heating rate was heated to 500 °C and N 2 The Cu content was 0.2, 0.9, 1.8, 8.0 and 10.8 wt.% 1 / PCN were prepared using 0.2, 1.0, 2.0, 10.0 and 15.0 wt.% Cu raw materials, respectively.
[0304] 7.3. Material characterization
[0305] Wide-angle X-ray diffraction (XRD) patterns were collected on a Bruker D8 focused powder X-ray diffractometer using Cu Ka radiation (40 kV, 40 mA) at room temperature. ADF-STEM imaging was performed on an aberration-corrected JEOL ARM-200F system equipped with a cold field emission gun operated at 60 kV. X-ray photoelectron spectroscopy (XPS) measurements were performed in a custom-designed ultrahigh vacuum system with a base pressure below 2 × 10 -10 mbar. Al Ka (hn = 1486.7 eV) was used as the excitation source for XPS. AFM images were acquired on a Bruker FastScan AFM using the Tapping mode. The metal content in all catalysts was measured by inductively coupled plasma atomic emission spectrometry (ICP-AES). FTIR spectra were performed at 25 °C on a Bruker Equinox 55 spectrometer equipped with a mercury cadmium telluride detector. X-band EPR spectra were obtained with a JEOL (FA200) spectrometer. Recorded on a Bruker Avance Neo 400 or 500 spectrometer 1 H. 13 C and 19 F NMR spectra. STM experiments were performed at 4.4K under UHV conditions (base pressure, <2×10 -9mbar) using a Scienta Omicron LT-STM system. According to Du, Y. et al., XAFCA: a new XAFS beamline for catalysis research. J. Synchrotron Radiat. 22, 839-843 (2015), the contents of which are fully incorporated herein by reference, X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) measurements were performed at the XAFCA beamline of the Singapore Synchrotron Light Source (SSLS). A Si (111) double crystal monochromator was used to filter the X-ray beam. High-resolution XANES was performed using the third harmonic of a Si (111) double crystal monochromator. Copper foil was used for energy calibration, and all samples were measured in transmission mode. According to Ravel, B. and Newville, M. ATHENA, ARTEMIS, HEPHAESTUS: data analysis for X-ray absorption spectroscopy using IFEFFIT, J. Synchrotron Radiat. 12, 537-541 (2005), the contents of which are fully incorporated herein by reference, the EXAFS oscillations χ (k) were extracted and analyzed using the Demeter software package. For the cross-coupling reactions, all reactants and catalysts were added to a nitrogen-filled glove box to avoid potential performance losses due to substrate instability in the presence of oxygen or, in particular, trace amounts of water.
[0306] 7.4. CN bond formation
[0307] An oven-dried screw-top reaction tube was equipped with a stir bar. Aryl halide (0.2 mmol), nitrogen-based nucleophile (0.24 mmol for N-heterocyclic compounds and 0.3 mmol for primary and secondary amines), Cu g / PCN (1.0 mg, 1.4 mol% Cu), 0.4 mmol base (K for N-heterocyclic compounds) 3 PO 4 , NaOH for primary and secondary amines) and anhydrous DMSO (1.0 mL). The reaction tube was sealed with a Teflon-lined screw cap, taken out of the glove box, placed in an oil bath preheated to 110° C. and stirred for 28 h. After cooling to room temperature, the reaction cap was removed, and the reaction mixture was concentrated in vacuo with the help of a rotary evaporator. The resulting residue was then purified by silica gel column chromatography to obtain the pure product.
[0308] 7.5. CO bond formation
[0309] An oven-dried screw-top reaction tube equipped with a stir bar was added sequentially with aryl iodide (0.2 mmol), alcohol (0.4 mmol, 0.8 mmol for dihalogenated aromatic rings), Cu g / PCN (1.0 mg, 1.4 mol% Cu), KOtBu (0.3 mmol, 0.6 mmol for dihalogenated aromatic rings) and anhydrous dioxane (2.0 mL). The reaction tube was sealed with a Teflon-lined screw cap, taken out of the glove box, placed in an oil bath preheated to 80° C. and stirred for 18 h. After cooling to room temperature (rt), the reaction cap was removed and the reaction mixture was concentrated in vacuo with the help of a rotary evaporator. The resulting residue was then purified by silica gel column chromatography to obtain the pure product.
[0310] 7.6. C-C bond formation
[0311] An oven-dried screw-top reaction tube was equipped with a stir bar. Aryl halide (0.2 mmol), alkyne (0.3 mmol, 0.6 mmol for dihalogenated aromatic rings), Cu g / PCN (1.0 mg, 1.4 mol % Cu), Cs(OH) 2 .H 2 O (0.3mmol, for dihalogenated aromatic rings, 0.6mmol) and anhydrous DMSO (1.0mL). The reaction tube was sealed with a Teflon-lined screw cap, taken out of the glove box, placed in an oil bath preheated to 110°C and stirred for 28h. After cooling to room temperature, the reaction cap was removed, and the reaction mixture was concentrated in vacuo with the help of a rotary evaporator. The resulting residue was then purified by silica gel column chromatography to obtain the pure product.
[0312] 7.7. CS bond formation
[0313] An oven-dried screw-top reaction tube equipped with a stir bar was added sequentially with aryl halide (0.2 mmol), thiol / thiophenol (0.3 mmol), Cu g / PCN (1.0 mg, 1.4 mol% Cu), NaOtBu (0.30 mmol) and anhydrous dioxane (2.0 mL). The reaction tube was sealed with a Teflon-lined screw cap, taken out of the glove box, placed in an oil bath preheated to 80° C. and stirred for 18 h. After cooling to room temperature, the reaction cap was removed and the reaction mixture was concentrated in vacuo with the help of a rotary evaporator. The resulting residue was then purified by silica gel column chromatography to obtain the pure product.
[0314] 7.8. Azide-alkyne cycloaddition
[0315] In a 10 mL glass tube, use Cu g / PCN catalyst (1 mg, 1.4 mol% Cu), 0.2 mmol arylacetylene, 0.6 mmol (1.2 mmol for diarylacetylene) benzyl azide, decane (0.2 mmol) and 3 mL 1: 1 water / acetonitrile mixture were subjected to azide-alkyne cycloaddition and stirred at 60°C for 24 hours. After cooling to room temperature, the mixture was diluted with water and extracted with DCM. The crude product was analyzed by gas chromatography-mass spectrometry (GC-MS) to determine the yield.
[0316] 7.9. Recirculation test
[0317] 4-iodotoluene (20.0 mmol, 4360 mg), ethanol (40.0 mmol, 1840 mg), Cu g / PCN (100mg, 1.4mol%Cu), KOtBu (30mmol, 3368mg), decane (10.0mmol, 1950μL) and anhydrous dioxane (200mL) were added to an oven-dried screw-top reaction bottle equipped with a stirring rod. The reaction bottle was sealed with a Teflon-lined screw cap, taken out of the glove box, placed in an oil bath preheated to 80°C and stirred for 8h. After cooling to room temperature, the bottle was allowed to stand for 1h. The reaction cap was then removed, and an aliquot of the solution was transferred to a vial, diluted with EtOAc, and analyzed by GC to determine the yield. The remaining reaction mixture was removed by vacuum filtration using a nylon filter membrane. Before being used for the next cycle reaction, the catalyst was washed three times in dioxane, EtOH and DI water, and dried overnight at 80°C.
[0318] 7.10. Continuous Flow Synthesis
[0319] The continuous flow reaction was carried out in a tubular reactor. 250 mg of Cu g / PCN (40-100 mesh particles) and 250 mg of quartz sand / diatomaceous earth at each end were loaded into a steel / quartz column reactor, and a mixture of reactants, base and solvent was pumped through the column at a certain flow rate. The real-time yield of the product was detected by GC-MS.
[0320] 7.11. In situ X-ray absorption spectroscopy
[0321] In a nitrogen-filled glove box, an oven-dried screw-top reaction tube equipped with a stir bar was added sequentially with 4-iodobenzene (1.0 mmol), ethanol (2.0 mmol), Cu g / PCN (5.0 mg), KOtBu (1.5 mmol) and anhydrous dioxane (5.0 mL). The reaction tube was sealed with a Teflon-lined screw cap, taken out of the glove box, placed in an oil bath preheated to 80°C and stirred for 3 h. Afterwards, the mixture was quickly transferred to a plastic bag for XAFS measurement.
[0322] 7.12. In situ electron paramagnetic resonance spectroscopy
[0323] In a nitrogen-filled glove box, an oven-dried quartz EPR tube was equipped with a stirring bar. 4-iodobenzene (0.05 mmol), ethanol (0.1 mmol), Cu g / PCN (4.0 mg), KOtBu (0.075 mmol) and anhydrous dioxane (0.5 mL). The reaction tube was sealed with a screw cap, taken out of the glove box and placed in an oil bath preheated to 80° C. with stirring. For each indicated time, the EPR tube was transferred from the oil bath to the EPR spectrometer and the corresponding measurement was performed. After collecting the data, the EPR tube was transferred back to the oil bath for continued reaction.
[0324] 7.13. Calculation details
[0325] Quantum chemical studies were performed at the level of Kohn-Sham density functional theory (DFT), using two theoretical formalisms, the periodic DFT approach and the molecular DFT approach, for selected cluster models. These two approaches provide more comprehensive computational data for understanding geometry, electronic structure, chemical bonding, and catalytic mechanisms. According to Kresse, G. and Furthmüller, J. Efficient iterative schemes for ab initio total-energy calculations using a plane-wave basis set, Phys. Rev. B 54, 11169 (1996), the contents of which are fully incorporated herein by reference, the Vienna Ab-initioSimulation Package (VASP) was used for periodic DFT calculations. According to Henkelman, G., Uberuaga, BP and Jónsson, H. Aclimbing image nudgedelastic band method for finding saddle points and minimum energy paths, J. Chem. Phys. 113, 9901-9904 (2000), the contents of which are fully incorporated herein by reference, these first-principles calculations under the spin-polarized Kohn-Sham formula were performed using CI-NEB (climbing image nudged elastic band) for structural optimization, electronic structure analysis and transition state searches.The generalized gradient approximation (GGA) in the Perdew-Burke-Ernzerhof (PBE) exchange-correlation functional according to Perdew, JP, Burke, K. and Ernzerhof, M. Generalized gradient approximation made simple. Phys. Rev. Lett. 77, 3865 (1996), the contents of which are fully incorporated herein by reference, the projector-augmented wave (PAW) method according to Kresse, G. and Joubert, D. From ultrasoft pseudopotentials to the projectoraugmented-wave method, Phys. Rev. B 59, 1758 (1999), the contents of which are fully incorporated herein by reference, and a plane wave basis set with a cutoff energy of 450 eV were used in all calculations. The convergence criteria for structural relaxation and CI-NEB were set to , respectively. and In the direction perpendicular to the PCN film, The vacuum layer is used to avoid artificial interactions between adjacent images. 5×5×1-k-point sampling is applied in all calculations. A 2×2 supercell of PCN structure is used to model the Cu-doped PCN 2D film. The supercell used in the calculation is as follows: Fig. 20A and Fig. 20B As shown. The adsorption energy is defined as E ads = E(adsorption)-E(separation), which means that the stronger the adsorption, the more negative the adsorption energy. The calculated charge density distribution (CDD) and partial wave density of states (PDOS) of carbon-nitrogen 2D materials doped with single-atom Cu and diatomic Cu (geminal) are shown in Fig.11A , Fig. 11B , Fig. 11C and Fig.11D shown.
[0326] like Fig. 20BAs shown, molecular DFT calculations are performed on the constructed cluster model to compare with periodic DFT calculations. According to Frisch, M. et al. (Gaussian, Inc. Wallingford, CT, 2016), the contents of which are fully incorporated herein by reference, using the Gaussian-16 program suite, spin-restricted and spin-unrestricted (polarized) Kohn-Sham calculations (RKS and UKS) are performed for closed-shell singlets and open-shell singlets / triplets, respectively. According to Francl, MM et al.'s self-consistent molecular orbital method (Self-consistent molecular orbital methods). XXIII. A polarization-type basis set for second-row elements, J. Chem. Phys. 77, 3654-3665 (1982), the contents of which are fully incorporated herein by reference, polarization splitting valence bonds (split-valence) 6-31G (d) high basis sets are used for C, N, O and H atoms. The effective core potentials of LANL2DZ according to Hay, PJ and Wadt, WR, Ab initio effective core potentials for molecular calculations, Potentials for K to Au including the outermost core orbitals, J. Chem. Phys. 82, 299-310 (1985), the contents of which are incorporated herein by reference in their entirety, were used for Cu, and the LANL2DZ basis set was used for Cu[Ne]3s 2 3p 6 3d 6 4s 2Valence electrons. In this work, harmonic vibration frequencies were obtained at the same level to check the properties of the stationary point. All structures discussed in this work are the minimum state or transition state on the corresponding potential energy surface, which is confirmed by zero or an imaginary frequency, respectively. In order to further refine the electronic energy, when according to Becke, AD has a density functional exchange energy approximation with correct asymptotic behavior (Density-functional exchange-energy approximation with correct asymptotic behavior), Physical review A 38, 3098 (1988) and Lee, C., Yang, W. and Parr, RG Colle-Salvetti correlation energy formula is developed into a function of electron density (Development of the Colle-Salvetti correlation-energy formula into afunctional of the electron density), Phys. Rev. B 37, 785 (1988) (its contents are fully incorporated herein by reference) when specified, the hybrid B3LYP functional is also used to perform single-point calculations on the optimized geometry. The study also plotted the radial distribution probability density of Cu(II) atomic orbitals (AOs) ( Fig. 22 ), D(r)=r 2 R(r) 2 , to elucidate the chemical bonding interactions of Cu···Cu when the distance changes.
[0327] The adsorption energy (E) of molecules (M) by GAC ads ) is defined as
[0328] E ads =E M-GAC -E GAC -E M
[0329] Where E M-GAC 、E GAC and E M are GAC with adsorbed M molecules, the total energy of GAC and adsorbed molecules, respectively.
[0330] In order to explore the catalytic reaction mechanism of various chemical reactions through GAC, the research selection focused on CO coupling reaction. 6 H 5 I and CH 3 As an example, the reaction between OH and Fig.21A , Fig.21B , Fig. 21C , Fig. 22, Fig.23 , Fig.24 and Fig.25 The energy distributions calculated using PBE functionalization for various pathways and processes are shown in 6 H 5 I and CH 3 Direct dehalogenation and dehydrogenation of OH and indirect dehalogenation and dehydrogenation assisted by strong base KOtBu were also explored. 6 H 5 and CH 3 There are two reaction pathways (indirect and direct pathways) for CO coupling between O* and CH. 3 O* and *C 6 H 5 The CO coupling forms C 6 H 5 OCH 3 The direct pathway is much more difficult than the direct pathway, in which CO coupling is promoted by the dynamic formation of direct Cu-Cu4s-4s bonds. The latter represents a new reaction mechanism for CO coupling via a disproportionation process of copper oxidation state from Cu(II)-Cu(II) to Cu(III)-Cu(I). The Cu in GAC is listed in Table 5. A ···Cu B The atomic numbers of the active sites and N atoms, as well as the calculated bond distances and Wiberg bond orders of the intermediate states IS5 and IS6. The open shell intermediates are listed in Table 7 3 IS3 and 3 The Mulliken spin density distribution of atoms in IS4 promotes the disproportionation of Cu A ···Cu B Assignment of oxidation states to active sites. Here, superscripts 1 and 3 (e.g., 3 IS3 and 3 IS4) represents the spin multiplicity of the system 2S+1.
[0331] Table 7 | Shell-opening intermediates 3 IS3 and 3 Mulliken spin density population of IS4
[0332]
[0333] 7.14. Life Cycle Assessment
[0334] According to ISO, I.14040, Environmental management life cycle assessment principles and framework (Environmental management-life cycle assessment-principles and framework), 235-248 (2006) and Standardization, 10f Environmental management: Life cycle assessment; Requirements and guidelines (Environmental management: life cycle assessment; requirements and guidelines), Vol. 14044 (ISO Geneva, Switzerland, 2006) (its content is fully incorporated herein by reference), Life cycle assessment (LCA) follows the four LCA stages in ISO 14040 / 44 standard. Target (step 1) is to assess the environmental impact of two optional catalytic pathways (i.e. heterogeneous catalysis and homogeneous catalysis) of the synthetic product 1 (1-(naphthalene-1-yl)-1H-imidazoles) via Ullmann type CN coupling reaction, as shown below. Both pathways used the same substrates (1-iodonaphthalene and 1H-imidazole) but implemented different reaction conditions, including solvents (dimethyl sulfoxide or N-methyl-2-pyrrolidone, respectively), to synthesize 1 kg of product 1 (functional unit). g / PCN GAC, whose homogeneous catalytic system consists of Cu 2 O and 4,7-dimethoxy-1,10-phenanthroline as a ligand (Cu 2 O+L 1 , Table 2). A cradle-to-gate scope was adopted, i.e. the LCA covered all emissions associated with upstream activities in the synthesis of substrates, solvents and catalysts for both systems, up to the generation of product 1, while omitting its subsequent use and disposal phase (which was identical in both cases). In the baseline scenario, it was assumed that there was no recycling of the reaction mixture in either route. However, the effect of reusing catalysts and solvents (i.e. reducing the required amounts of these components) was explored in a sensitivity analysis considering up to 100 cycles ( Fig.36A and Fig.36B ).
[0335] In the life cycle inventory (LCI, step two), the study used experimental values supplemented by mass balances based on stoichiometric coefficients of upstream synthesis steps to estimate the entire range of inputs in the foreground system. Essentially, mass balances were recursively applied in the synthesis tree of two catalysts and one reactant (i.e., 1-iodonaphthalene) until reaching compounds available in ecoinvent v3.9 according to Wernet, G. et al., The ecoinvent database version 3 (part I): overview and methodology, The International Journal of Life Cycle Assessment 21, 1218-1230 (2016) (the contents of which are fully incorporated herein by reference), from which background data on surrounding activities providing inputs to the foreground system were retrieved using cutoff modeling selections (more details in https: / / ecoinvent.org / the-ecoinvent-database). In the life cycle impact assessment phase (LCIA, step 3), the study calculated the 100-year global warming potential (GWP100) in kilogram equivalent (kg CO2-eq) as a unit, taking into account short-lived climate forcing factors (SLCF). To this end, the study follows the Intergovernmental Panel on Climate Change (IPCC 2021) of the United Nations, which estimates the potential for climate change caused by greenhouse gas emissions (GHG) according to Forster, P. et al. The Earth's energy budget, climate feedbacks, and climate sensitivity, (2021) (the contents of which are fully incorporated herein by reference). In addition, the study supplemented the impact analysis with the endpoints of ReCiPe 2016 according to Huijbregts, MA et al. ReCiPe 2016: a harmonised life cycle impact assessment method at midpoint and endpoint level, The International Journal of Life Cycle Assessment 22, 138-147 (2017) (the contents of which are fully incorporated herein by reference), assessing damage to three main areas of protection; human health, ecosystem quality and resource availability. Finally, in the fourth LCA phase, the results were interpreted, hot spots were identified, and conclusions and recommendations were provided. All LCA calculations were implemented in Brightway2 v2.4.1 according to Mutel, C. Brightway: an open source framework for life cycle assessment, Journal of Open Source Software2, 236 (2017) (the contents of which are fully incorporated herein by reference).
[0336] 7.15. Assumptions and limitations of the LCA approach
[0337] The LCA relies on a set of assumptions, as described below, which the inventors believe do not affect the main conclusions.
[0338] 1. The study omits the utilities required for the reaction steps in the prospective system. Exothermic reactions may require cooling water to control reactor temperature, the effect of which tends to be negligible (especially if the cooling water is circulated), while endothermic reactions will require steam. The study also notes that heat integration is very challenging in a batch process, which would likely be preferred for this reaction system. Therefore, it is difficult to use the heat generated in the exothermic reaction to obtain environmental credits, which is omitted in our analysis.
[0339] 2. The study further assumes that the final product can be easily separated from the reaction mixture without any energy loss. In practice, the study should scale up the separation step using suitable unit operations. However, this separation was not attempted on a laboratory scale, so the study lacks an experimental basis for scale-up calculations. The study notes that both routes require such a separation step, so it is likely that the relevant impacts will be similar and the comparative evaluation will lead to the same conclusions. In addition, the homogeneous system may require an additional step of separating the catalyst from the reaction mixture, which was also omitted, further underestimating its impact.
[0340] 3. Similarly, this study omitted the required separations in the different synthesis steps of the catalyst components and 1-iodonaphthalene in the foreground system. Note that this study employed the same simplification, i.e., omitting the effects of separations in the synthesis of both catalytic systems, thereby underestimating the effects in both cases.
[0341] 4. The study considers that the data from the background systems retrieved from Ecoinvent accurately depict the life cycle activities associated with the catalytic systems. To do this, the study selected a global market that represents global average data. This is a common assumption in many studies that use the same representation of time and technology levels as in the database.
[0342] Overall, this study provides lower bounds (i.e., optimistic estimates) on the total impact for each case, since some impact contributions are neglected, such as the utility and impact of the separation steps. However, this study expects that the estimates will be close to the actual total impacts, since these are typically dominated by the raw materials (explicitly accounted for in our LCA), as occurs in the heterogeneous case, while other contributions tend to be significantly lower. Furthermore, the same assumptions were applied in both catalytic systems, so potential errors in the approximation can cancel out, resulting in similar relative performance.
[0343] Those skilled in the art will appreciate that other changes and / or modifications may be made to the embodiments disclosed herein without departing from the spirit or scope of the present disclosure as broadly described. For example, in the description herein, features of different exemplary embodiments may be mixed, combined, interchanged, incorporated, adopted, modified, or included, etc. across different exemplary embodiments. Therefore, the present embodiments are considered in all respects to be illustrative and not restrictive.
Claims
1. A material comprising a plurality of geminal metal atom pairs supported on a polymer support.
2. The material of claim 1, wherein each geminal metal atom pair comprises two single metal atoms that are not bonded to each other.
3. The material of claim 2, wherein the two single metal atoms are each bound to a different metal coordination site of the polymer support.
4. The material according to any one of claims 2 and 3, wherein the average distance between the two single metal atoms is to 5. A material according to any one of the preceding claims, wherein each single metal atom is diagonally bonded to two different metal coordination sites of the polymer support.
6. The material according to any one of the preceding claims, wherein the material comprises a structure represented by the general formula (1); and a structure represented by the general formula (2): –A 1 -M 1 -A 2 -(1) –A 3 -M 2 -A 4 -(2) in M 1 and M 2 Each is independently a single metal atom; M 1 and M 2 The two form a geminal metal atom pair; and A 1 , A 2 , A 3 and A 4 Each is independently a metal coordination site of the polymer support.
7. A material according to any preceding claim, wherein the material comprises 0.1 wt% to 50.0 wt% metal.
8. The material of any one of the preceding claims, wherein the metal comprises a transition metal selected from the group consisting of copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), iron (Fe), manganese (Mn), chromium (Cr), vanadium (V), titanium (Ti), scandium (Sc), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), lanthanum (La), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), gold (Au), mercury (Hg), actinium (Ac), and combinations thereof.
9. A material according to any preceding claim, wherein the metal is monovalent.
10. The material of any one of the preceding claims, wherein the polymer carrier comprises an organic polymer comprising one or more atoms selected from the group consisting of carbon, nitrogen, phosphorus, sulfur, and combinations thereof.
11. The material according to any one of the preceding claims, wherein the polymer carrier comprises a polymer chain having two or more fused triazine rings.
12. The material of any one of the preceding claims, wherein the material comprises a first shell comprising the metal atoms and first atoms of the polymer support.
13. The material of claim 12, wherein the interatomic distance between the metal atom in the first shell and the first atom of the polymer support is to 14. The material of any one of the preceding claims, wherein the material comprises a second shell comprising the metal atoms and second atoms of the polymer support.
15. The material of claim 14, wherein the interatomic distance between the metal atoms in the second shell and the second atoms of the polymer support is to 16. A catalyst comprising a material according to any one of the preceding claims.
17. A method for catalyzing a coupling reaction, the method comprising: (ai) providing a material according to any one of claims 1 to 15; and (a-ii) mixing the material with two or more reactants to be coupled to obtain a coupling product.
18. The method of claim 17, wherein the coupling reaction comprises a cross-coupling reaction, a cross-coupling bond formation, a cycloaddition, a carbon-carbon bond formation, a carbon-heteroatom bond formation, an N-arylation, or a combination thereof.
19. The method according to any one of claims 17 to 18, wherein the reactant is selected from the group consisting of: heteroaryl halides, aryl halides, substrates containing one or more hydroxyl groups, substrates containing one or more amino groups, substrates containing one or more amide groups, substrates containing one or more sulfonamide groups, substrates containing one or more alkynyl groups, substrates containing one or more thiol groups, substrates containing one or more electron-rich aromatic groups, substrates containing one or more electron-poor aromatic groups, alcohols, halogenated alcohols, deuterated alcohols, heterocyclic compounds, alkynes, thiols, azides, acetylenes, L-menthol, DL-menthol, stigmasterol, DL-isoborneol, galactose, 1,2,3,4-diacetonegalactose, testosterone, prednisolone, derivatives thereof, and combinations thereof.
20. A method for preparing a material according to any one of claims 1 to 15, the method comprising: (i) reacting a metal source with a polymer support to obtain the material; and (ii) separating the materials.
21. The method of claim 20, wherein the method further comprises the step of exfoliating the material into nanostructures.
22. The method of any one of claims 20 to 21, wherein the metal source comprises a metal salt selected from the group consisting of metal chlorides, metal fluorides, metal bromides, metal iodides, metal oxides, metal sulfates, metal sulfides, metal cyanides, metal thiocyanates, metal acetylides, metal acetates, metal hydroxides, metal hydrides, metal nitrates, metal phosphides, metal phosphates, metal carbonates, metal carbonate hydroxides, metal chlorates, metal arsenates, metal azides, metal acetylacetonates, metal perchlorates, metal triflates, metal tetrafluoroborates, metal benzoates, metal chromites, metal peroxides, and combinations thereof.
23. The method of any one of claims 20 to 22, wherein the metal source comprises a divalent metal cation.
24. A method according to any one of claims 20 to 23, wherein the step of reacting comprises adding 0.1 wt% to 50.0 wt% of the metal source.
25. The method of any one of claims 20 to 24, wherein the step of reacting comprises adding 50.0 wt% to 99.9 wt% of the polymer carrier.